Polyunsaturated fatty acid metabolism in the retinal pigment epithelium and its association with outer retinal disease - Naga Pradeep Rayana; Navdeep Gogna; Mark P. Krebs; Gayle B. Collin; Jürgen K. Naggert; Patsy M. Nishina (Mammalian Genome, 2026)
Polyunsaturated fatty acids (PUFAs) are essential for photoreceptor (PR) development, structure and function, and their availability in the outer retina is predominantly mediated by the retinal pigment epithelium (RPE), a cellular monolayer juxtaposed to the PR outer segments. Because PRs lack enzymatic machinery to generate critical PUFA intermediates from dietary precursors, they rely on the RPE to coordinate multiple steps of PUFA uptake, metabolism and export. Consequently, disruption in any of these steps perturbs PR homeostasis and compromises overall retinal health. In this review, we summarize current evidence about the genes, proteins, molecular pathways, and pathological alterations that govern the regulation of PUFA metabolism in the RPE. Data from human genetic disorders, mouse models and in vitro studies is discussed to illustrate how disruption of PUFA pathways in the RPE leads to lipid imbalance and retinal degeneration, and to highlight how these findings illuminate molecular mechanisms underlying PUFA biology. We also identify critical gaps in knowledge and unresolved questions surrounding RPE-PR PUFA metabolism and propose that addressing these gaps will be essential for advancing therapeutic strategies for retinal disease.

Microplate subdivision, terrane identification and intra-terrane stratigraphic framework of the Arabian Shield—volcanic arcs priming the planet for the Cryogenian? - Alan S. Collins; Mahrous M. Abu El-Enen; Pierre Nehlig; Paul H. Macey; Joachim Jacobs; Cees W. Passchier; Fayek H. Kattan; Martin J. Whitehouse; Rami A. Bakhsh; Saad M. Al Garni; Mohammed B. Elkomi; Peter R. Johnson; et al. (Earth-Science Reviews, 2026)

Waste heat recovery from a retrofitted generator using a thermoelectric generator (TEG) - Collins N. Nwaokocha; Daniel J. Poheto; Abayomi T. Layeni; Amos B. Ogunfowora; Olanrewaju S. Olasanmi; Oguntola J. Alamu; Mohsen Sharifpur (Next Research, 2026)

White wine, sparkling white wine and black caviar – The sensory experience of pairing of flavours - K. Wendin; B. Collin; S. Forsberg; H. Scander; R. Albin; F. Åhrberg; T. Ranta (International Journal of Gastronomy and Food Science, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

The Test-Retest Reliability of Non-Navigated Transcranial Magnetic Stimulation (TMS) Measures of Corticospinal Pathway Excitability in a Neurologically Intact Adult Population - Kathryn C. Collins; Allan B. Clark; Valerie M. Pomeroy; Niamh C. Kennedy (Brain Topography, 2026)
The test-retest reliability of Transcranial Magnetic Stimulation (TMS) measurements in healthy adults across the lifespan remains unclear. Determine the test-retest reliability and smallest detectable change (SDC) of motor evoked potential, (MEP), characteristics elicited by non-neuro-navigated Transcranial Magnetic Stimulation in neurologically intact adults. In two identical data collection sessions separated by five to seven days in a healthy adult sample was conducted. MEP characteristics assessed were motor threshold (MT) (rest and active conditions), amplitude (active), latency (MEP-L) (active conditions), silent period (SP) (active conditions), and recruitment curve (RC) (active conditions). Muscles investigated were bilateral biceps brachii (BB), extensor carpi radialis (ECR), and abductor pollicis brevis (APB). Test-retest reliability was calculated using the intra-class correlation coefficient (ICC) with corresponding 95% confidence intervals (CI) and limits of agreement (LOA), and the smallest detectable change was calculated. Acceptable reliability was set at a lower 95% CI of 0.70 or above for the ICC. In healthy adults ( n = 51) none of the MEP characteristics were reliable. The lower end of the CI was below acceptable reliability (ICC < 0.7) for all MEP characteristics. Active MT of the non-dominant biceps was most reliable (e.g. ICC = 0.78[0.64–0.87]); whereas the RC demonstrated poor reliability for all muscles. The LOA had small mean differences between sessions with wide 95% LOA demonstrating measurement variability. The SDC were variable across muscles and MEP characteristics. In this study the findings indicate there is still limited evidence for acceptable reliability of TMS outcomes which are interpreted by the lower end of the 95% CI of the ICC.

A Review of 35 Years in Developing Constitutive Models for the Callovo-Oxfordian Claystone Behavior - M. N. Vu; G. Armand; J. Talandier; C. Plua; M. Souley; J. F. Shao; Z. Yu; J. B. Colliat; J. Vaunat; A. Gens; S. Olivella; F. Collin; et al. (Rock Mechanics and Rock Engineering, 2026)

Backward scrunching: planarians escape from noxious stimuli, cannibalism, and predation - Liesel Blau; Hannah Poon; Nayana S. Tellakula; Katherine C. Hallmark; Erin Szuromi; Evangeline Coffinas; William B. Kristan; Eva-Maria S. Collins (Journal of Comparative Physiology A, 2026)
Animals have evolved escape behaviors to survive. Freshwater planarians have many predators, including conspecifics in cannibalistic species such as Dugesia japonica . When agitated, planarians escape via a locomotory behavior called “scrunching”, whereby the planarian periodically elongates and contracts its whole body. Current understanding is that planarians move forward when they scrunch. However, when transversely cutting D. japonica , we observed that while head pieces scrunched forward, tail pieces scrunched backward instead. Previous work has shown that forward scrunching is a conserved planarian escape behavior in response to transection and adverse stimuli such as low pH, noxious heat, hydrogen peroxide, and allyl isothiocyanate. Testing these stimuli, we found that backward scrunching is more difficult to induce than forward scrunching in both intact planarians and pieces. Using electrostimulation, we show that behavior progresses with increasing voltage from turning to backward scrunching to flailing when stimulated anteriorly, demonstrating that backward scrunching is a response to moderately strong stimuli. Moreover, we show that tail pieces – originating from transection or asexual reproduction (fission) - exhibit backward scrunching when attacked by intact planarians. Backward scrunching and backward steps of tail pieces were also observed when worms were bitten into pieces by dragonfly or damselfly nymphs, natural predators of planarians. The survival of tail pieces after fission is necessary for the expansion of asexual planarian populations. Thus, we propose that backward scrunching serves as an effective escape behavior to protect planarian tails from being eaten.

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The detrital zircon record of the Mesoproterozoic Renner Group, Tomkinson Province, northern Australia: correlations within the greater McArthur Basin - M. L. Blades; T. J. Munson; A. de Groot; A. S. Collins; D. Subarkah; A. Nixon; B. Yang (Australian Journal of Earth Sciences, 2026)

Orogens and detritus: unravelling the Mesoproterozoic tectonic geography of northern Australia through coupled detrital thermo- and geo-chronometers - B. Yang; A. S. Collins; M. L. Blades; F. Jourdan (Australian Journal of Earth Sciences, 2026)

Title: The evaluation of ruminal undegradable protein supplementation level on growth performance and ovarian development in beef heifers grazing native rangelands. - Taylor N. Andrews; Maria K. Chavez; Emily A. Melchior; Collin Anderson; Alexis B. Tamez; Shelby L. Rosasco; Shad H. Cox; Richard L. Dunlap; Robert A. Cushman; Jennifer A. Hernandez-Gifford; Eric J. Scholljegerdes; Adam F. Summers (Animal Reproduction Science, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Early Cretaceous freshwater bivalves from northeastern Brazil: Insights into the evolutionary history of South American freshwater mussels - Victor R. Silva; Vitor B. Guerrini; Filipe G. Varejão; Rafael C. Silva; Katie Collins; Ismar S. Carvalho; Simon Schneider; Marcello G. Simões (Cretaceous Research, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Impact of fertilization strategies on Phytolacca americana phytoextraction of rare earth elements from modified bauxite residue - Y. Lamwati; S. Criquet; A. Smouni; B. Angeletti; M. Le Bris; C. Levard; M. Fahr; B. Collin (International Journal of Environmental Science and Technology, 2026)

Exploring the intricacies of indoor dust pollution from neonicotinoid insecticides and its human health impacts: An exemplar from eleven agricultural communities in Ghana, West Africa - Collins NIMAKO; Osei AKOTO; Nathaniel BOADI; Prince OFORI; Yared B. YOHANNES; Shouta M.M. NAKAYAMA; Yoshinori IKENAKA; Mayumi ISHIZUKA (Journal of Hazardous Materials, 2025)

A systematic review and meta-analysis of the effectiveness of work-focused interventions for employees with symptoms of depression, anxiety, and psychological distress - Samineh Sanatkar; Rosie Lipscomb; Katherine Petrie; Daniel Collins; Andrew Arena; Mei Xu; Isabelle Counson; Vita Ligaya Dalgaard; Arnstein Mykletun; Anthony D. LaMontagne; Samuel B. Harvey; Mark Deady (International Archives of Occupational and Environmental Health, 2025)

Application of fin tissue for nonlethal stable isotope analysis of small-bodied fishes - Wade M. Wilson; Jane S. Rogosch; Scott F. Collins; Bart W. Durham; Kevin B. Mayes; Sarah M. Robertson (Environmental Biology of Fishes, 2025)
Stable isotopes are commonly used to characterize food web structure and resource use by aquatic organisms. White muscle is generally preferred for stable isotope analysis of fishes. However, obtaining white muscle tissue typically requires lethal take or invasive sampling techniques, which are undesirable for small-bodied species or those of conservation concern. We assessed the use of fish fin as a nonlethal alternative to muscle tissue for stable isotope analysis of four small-bodied fishes native to the upper Red River drainage of Texas and Oklahoma, USA: plains minnow Hybognathus placitus , prairie chub Macrhybopsis australis , Red River shiner Alburnops bairdi , and Red River pupfish Cyprinodon rubrofluviatilis . Fin isotope values were strong predictors of both δ 15 N and δ 13 C muscle isotope values (ANCOVA: δ 15 N: F 1,451 = 5312.09, P < 0.001; δ 13 C: F 1,451 = 7864.39, P < 0.001), although isotopic composition varied among species for δ 13 C ( F 3,451 = 4.29, P < 0.01). Species-specific regression models indicated positive linear relationships between fin and muscle isotope values (δ 15 N: P < 0.001, R 2 ≥ 0.80; δ 13 C: P < 0.001, R 2 ≥ 0.83) that did not vary significantly with body size or age of individuals. We suggest minimum total length thresholds for least destructive fin clipping at 70 mm, 62 mm, and 48 mm for plains minnow, prairie chub, and Red River pupfish, respectively. Nonlethal fin clipping may not be viable for Red River shiner within the size range reported here as multiple fins were required for routine analysis. Overall, we conclude that fin tissue may be used for δ 15 N and δ 13 C assessments to mitigate lethal take of imperiled, small-bodied fishes.

Open problems in ageing science: a roadmap for biogerontology - Angelo Talay; Aleksey V. Belikov; Paul Ka Po To; Hamid H. Alfatemi; Uri Alon; Joris Deelen; Collin Y. Ewald; David Gems; Vera Gorbunova; Jan Gruber; Sara Hägg; John Hemming; et al. (GeroScience, 2025)

Factors affecting short-term post-release survival probability of Lake Trout implanted with acoustic telemetry transmitters - Alexander J. Gatch; Dimitry Gorsky; Kyle T. Morton; R. Josephine Johnson; Collin J. Farrell; Timothy B. Johnson; Emma J. Bloomfield; Brent Metcalfe; Jessica Goretzke; Michael Connerton; Sarah M. Larocque; Jonathan D. Midwood; et al. (Fisheries Research, 2025)

Linking soil-metal concentrations with children's blood and urine biomarkers in Syracuse, NY - Dustin T. Hill; Michael Petroni; Vikrant Jandev; Kestutis Bendinskas; Lynn S. Brann; James A. MacKenzie; Christopher D. Palmer; Patrick J. Parsons; Mary B. Collins; Brooks B. Gump (Environmental Research, 2025)

Modelling and mapping of subsurface nitrate-attenuation index in agricultural landscapes - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne (Journal of Environmental Management, 2025)

10Be reproducibility in the Santa Monica Mountains, California, USA: A longitudinal study in a scorched and soaked landscape - Eric W. Portenga; Kirk F. Townsend; Lee B. Corbett; Paul R. Bierman; Marc W. Caffee; Collin Bogoski; Colin O'Neill; Samantha Skora (Geomorphology, 2025)

Effects of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of odors when trained with multiple explosives classes - S.A. Kane; G.N. Cupp; B. Rogers; D. Copeland; C. Collins-Pisano; J. Davis-Miller; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; J. Denapoli; P.A. Prada-Tiedemann; N.J. Hall (Applied Animal Behaviour Science, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Pollution and partitioning of neonicotinoid insecticides in free-grazing ducks and their eggs: Implications for human health - Collins Nimako; Kraisiri Khidkhan; Sittinee Kulprasertsri; Saranya Poapolathep; Paphatsara Khunlert; Yared B. Yohannes; Yoshinori Ikenaka; Shouta M.M. Nakayama; Mayumi Ishizuka; Amnart Poapolathep (Environmental Pollution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The effect of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of smokeless powders - S.A. Kane; G.N. Cupp; M. Rangel; A. Medrano; J. Davis-Miller; C. Collins-Pisano; B. Rogers; D. Copeland; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; P.A. Prada-Tiedemann; et al. (Applied Animal Behaviour Science, 2025)

Educating healthcare workers in snakebite management: A study to determine the effectiveness of the snake bite life support workshop - Aravind Sreekumar; Siju V. Abraham; P.C. Rajeev; Vijay Chanchal A. B; Appu Suseel; Deo Mathew; Collin R. George; Babu U. Palatty (Toxicon, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Assessment of spatial variability and temporal stability of groundwater redox conditions in New Zealand - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne; Jon K. F. Roygard (Environmental Monitoring and Assessment, 2024)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Perspectives on inclusion, safety, and belonging from members of the North American LGBTQIA+ conservation community - Amy C. Collins; Abigail B. Feuka; Jasmine Nelson; Anahita K. Verahrami; Sara Bombaci (Conservation Biology, 2024)
Conservation scientists work in diverse settings, sometimes requiring them to exist in spaces where they do not feel safe, included, or accepted. This is often the case for the LGBTQIA+ (lesbian, gay, bisexual, transgender, queer, questioning, intersex, asexual, and others) community, which is frequently marginalized in conservation spaces. We conducted an anonymous, semistructured, online survey of members and nonmembers of the LGBTQIA+ community of conservation students and professionals in North America to explore participants’ lived experiences in conservation. Our 737 responses (response rate 26.8%) included 10% who identified as genderqueer, gender nonconforming, questioning, nonspecific, genderfluid, transgender woman, agender, transgender man, 2‐spirit Indigenous, or intersex ( gender expansive ), and 29% as bisexual, queer, lesbian, gay, asexual, pansexual, omnisexual, questioning, or nonheterosexual ( queer+ ). We found that non‐LGBTQIA+ respondents overestimated the degree to which LGBTQIA+ respondents felt included in the field of conservation by 5% (sexual orientation) and 18% (gender identity). Respondents’ feelings of safety and belonging were up to 50% lower in most work settings compared with non‐LGBTQIA respondents; the lowest frequencies were reported by gender expansive respondents (40.9–64.4%). Contextual responses indicated that the lack of safety and belonging related to direct experiences of bullying (23 long‐form descriptions out of 73 gender expansive respondents and 15 of 217 queer+ respondents), concerns around safety in rural settings (4 of 73 gender expansive respondents and 20 of 217 queer+ respondents), and concerns around not being able to express their authentic selves (7 of 73 gender expansive respondents and 5 of 217 queer+ respondents). The intersection between gender identity and race also played a role in feelings of safety, belonging, and disclosure of sexual orientation (1 of 73 gender expansive respondents, 6 of 217 queer+ respondents). The most frequent support resources used by LGBTQIA+ conservation scientists included one‐on‐one support from peers, mentors and external collaborators, support group, and wellness and counseling services outside of work.

Quantifying spatial peat depth with seismic micronodes and the implications for carbon stock estimates - Jack B. Muir; Simon Jeffery; Joe Collins; Alice Marks; Nathan Brake; Tarje Nissen-Meyer (Science of The Total Environment, 2024)

Moths are less attracted to light traps than they used to be - Ian Battles; Eric Burkness; Michael S. Crossley; Collin B. Edwards; Kristian Holmstrom; William Hutchison; Joseph Ingerson-Mahar; David Owens; Avalon C.S. Owens (Journal of Insect Conservation, 2024)
As evidence of global insect declines continues to mount, insect conservationists are becoming increasingly interested in modeling the demographic history of at-risk species from long-term survey data. However, certain entomological survey methods may be susceptible to temporal biases that will complicate these efforts. Entomological light traps, in particular, may catch fewer insects today than they once did due solely to increases in anthropogenic light pollution. Here we investigate this possibility by comparing the demographic histories of corn earworm moths ( Helicoverpa zea ) estimated from pairs of blacklight and pheromone traps monitored at the same farms. We find a stark decline in blacklight trap efficacy over 25 years of monitoring in Delaware, USA, mirrored over 10 years of monitoring in New Jersey, USA. While the precise causes of this decline remain a subject for discussion, the practical consequences are clear: insect conservationists cannot fully rely on long-term trends from entomological light traps.

Occupancy of Sympatric Central Chimpanzee (Pan troglodytes troglodytes) and Western Lowland Gorilla (Gorilla gorilla gorilla) in Campo Ma’an Conservation Area, Southern Cameroon - Emily Collins; Robert B. Weladji (International Journal of Primatology, 2024)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

Padded Helmet Shell Covers in American Football: A Comprehensive Laboratory Evaluation with Preliminary On-Field Findings - Nicholas J. Cecchi; Ashlyn A. Callan; Landon P. Watson; Yuzhe Liu; Xianghao Zhan; Ramanand V. Vegesna; Collin Pang; Enora Le Flao; Gerald A. Grant; Michael M. Zeineh; David B. Camarillo (Annals of Biomedical Engineering, 2024)

Protective immunity induced through two calving seasons following administration of live epizootic bovine abortion agent (EBAA) vaccine - Myra T. Blanchard; Mike B. Teglas; Kassidy M. Collins; Mark L. Anderson; Bret R. McNabb; Jeffrey L. Stott (Veterinary Immunology and Immunopathology, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Wildfire burn severity and stream chemistry influence aquatic invertebrate and riparian avian mercury exposure in forested ecosystems - Garth Herring; Lora B. Tennant; James J. Willacker; Matthew Johnson; Rodney B. Siegel; Julia S. Polasik; Collin A. Eagles-Smith (Ecotoxicology, 2024)

Icequake insights on transient glacier slip mechanics near channelized subglacial drainage - Nathan T. Stevens; Lucas K. Zoet; Dougal D. Hansen; Richard B. Alley; Collin J. Roland; Emily Schwans; Cameron S. Shepherd (Earth and Planetary Science Letters, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Ecological indicators and source diagnostic ratios of aliphatic and polyaromatic hydrocarbons in marine sediments of Qatar - Maryam A. Abdulla; Azenith B. Castillo; Christopher Collins; Tom Sizmur (Regional Studies in Marine Science, 2023)

Using airborne thermal imaging to understand American Coot movement patterns in a hot spring refugium during winter - Justin H. White; Collin S. Philipps; Landon B. Chandler (Wetlands Ecology and Management, 2023)

Resource quantity and quality differentially control stream invertebrate biodiversity across spatial scales - Benjamin B. Tumolo; Sarah M. Collins; Yawen Guan; Amy C. Krist (Ecology Letters, 2023)
Resource quantity controls biodiversity across spatial scales; however, the importance of resource quality to cross‐scale patterns in species richness has seldom been explored. We evaluated the relationship between stream basal resource quantity (periphyton chlorophyll a ) and invertebrate richness and compared this to the relationship of resource quality (periphyton stoichiometry) and richness at local and regional scales across 27 North American streams. At the local scale, invertebrate richness peaked at intermediate levels of chlorophyll a , but had a shallow negative relationship with periphyton C:P and N:P. However, at the regional scale, richness had a strong negative relationship with chlorophyll a and periphyton C:P and N:P. The divergent relationships of periphyton chlorophyll a and stoichiometry with invertebrate richness suggest that autochthonous resource quantity limits diversity more than quality, consistent with patterns of eutrophication. Collectively, we provide evidence that patterns in resource quantity and quality play important, yet differing roles in shaping freshwater biodiversity across spatial scale.

Valuable bycatch: Eliciting social importance of sharks in Sri Lanka through value chain analysis - Claire Collins; Tom B. Letessier; Aloka Benaragama; Annette Broderick; Isuru Wijesundara; Dilhara Wijetunge; Ana Nuno (Marine Policy, 2023)

Postfire hydrologic response along the Central California (USA) coast: insights for the emergency assessment of postfire debris-flow hazards - Matthew A. Thomas; Jason W. Kean; Scott W. McCoy; Donald N. Lindsay; Jaime Kostelnik; David B. Cavagnaro; Francis K. Rengers; Amy E. East; Jonathan Y. Schwartz; Douglas P. Smith; Brian D. Collins (Landslides, 2023)
The steep, tectonically active terrain along the Central California (USA) coast is well known to produce deadly and destructive debris flows. However, the extent to which fire affects debris-flow susceptibility in this region is an open question. We documented the occurrence of postfire debris floods and flows following the landfall of a storm that delivered intense rainfall across multiple burn areas. We used this inventory to evaluate the predictive performance of the US Geological Survey M1 likelihood model, a tool that presently underlies the emergency assessment of postfire debris-flow hazards in the western USA. To test model performance, we used the threat score skill statistic and found that the rainfall thresholds estimated by the M1 model for the Central California coast performed similarly to training (Southern California) and testing (Intermountain West) data associated with the original model calibration. Model performance decreased when differentiating between “minor” and “major” postfire hydrologic response types, which weigh effects on human life and infrastructure. Our results underscore that the problem of false positives is a major challenge for developing accurate rainfall thresholds for the occurrence of postfire debris flows. As wildfire activity increases throughout the western USA, so too will the demand for the assessment of postfire debris-flow hazards. We conclude that additional collection of field-verified inventories of postfire hydrologic response will be critical to prioritize which model variables may be suitable candidates for regional calibration or replacement.

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

Fuel reduction burning reduces wildfire severity during extreme fire events in south-eastern Australia - L. Collins; R. Trouvé; P.J. Baker; B. Cirulus; C.R. Nitschke; R.H. Nolan; L. Smith; T.D. Penman (Journal of Environmental Management, 2023)

The effect of shear-dependent flocculation on the multimodality of effective particle size distributions in a gravel-bed river during high flows - R. Maltauro; M. Stone; A. L. Collins; B. G. Krishnappan; U. Silins (Journal of Soils and Sediments, 2023)
Purpose Multimodal effective particle size distributions (EPSDs) develop as flocculation and particle breakage occur dynamically in a fluid shear and such distributions have been previously reported in coastal and estuarine waters to understand flocculation processes. Here, we use time varying multimodal EPSDs and hydraulic parameters (discharge and bed shear stress) to assess freshwater flocculation in a gravel-bed river in southern Alberta, Canada. Methods Instantaneous discharge, volume concentration (VC), and EPSD of suspended solids were measured during three high discharge events at four study sites in a 10 km reach of the Crowsnest River. The EPSD and VC of suspended solids (< 500 µm) were measured in the centroid of flow with a LISST-200x. Bed shear stress for measured discharge was obtained using a flow model, MOBED. Results Multimodal EPSDs consisted of primary particles, flocculi, microflocs, and macroflocs. Shear dependent flocculation was consistently observed for all sites and events, due to low and high shear stress flocculation, particle breakage, and mobilization of tributary sub-catchment derived particles. Higher shear stress limited flocculation to smaller floc sizes, while lower bed shear stress conditions created higher volumes of macroflocs. Conclusion Flocculation and particle breakage processes based on relationships between particle size and hydraulic properties presented herein have implications for advancing fine sediment transport models by a variable cohesion factor as a function of floc size class.

Virtual Group Visit Nutrition Program Increases Productivity and Provides a Positive Patient Experience - E. Collins; S. Bouma; B. Kuznicki; E. Scarlett (Journal of the Academy of Nutrition and Dietetics, 2023)

Understanding drivers of mercury in lake trout (Salvelinus namaycush), a top-predator fish in southwest Alaska's parklands - Krista K. Bartz; Michael P. Hannam; Tammy L. Wilson; Ryan F. Lepak; Jacob M. Ogorek; Daniel B. Young; Collin A. Eagles-Smith; David P. Krabbenhoft (Environmental Pollution, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Mammalian organ regeneration in spiny mice - Daryl M. Okamura; Elizabeth D. Nguyen; Sarah J. Collins; Kevin Yoon; Joshua B. Gere; Mary C. M. Weiser-Evans; David R. Beier; Mark W. Majesky (Journal of Muscle Research and Cell Motility, 2023)

Dorsal Fin Spines and Rays for Nonlethal Ageing of Goliath Grouper Epinephelus itajara - Jessica L. Carroll; Robert D. Ellis; Angela B. Collins; Debra J. Murie (Fishes, 2023)
Atlantic Goliath Grouper, Epinephelus itajara, the largest grouper in the western North Atlantic, exhibits life history characteristics (e.g., it is slow-growing, long-lived, and late-maturing) that make it particularly susceptible to fishing pressure. Otoliths, the structure typically processed for age determination, are usually collected as part of fishery monitoring, but otoliths are not available from Goliath Grouper due to a harvest moratorium enacted in 1990 for United States waters. Alternative structures—such as dorsal fin rays or spines—can be acquired for ageing via nonlethal sampling and may provide reliable age estimates. Since 2006, the Florida Fish and Wildlife Conservation Commission (FWC) has been collecting incidental Goliath Grouper samples from mortality events including those from cold kills and red tides. Corresponding otolith, dorsal fin ray and dorsal fin spine samples were compared to determine the accuracy and precision of the external ageing structures. Marginal increment analyses indicated that annulus (translucent zone) deposition occurred primarily in March–June on spines and in April–June on rays. While ages determined from both rays and spines exhibited high precision, the accuracy compared to otolith ages was low as a result of systematic underageing of both external structures, particularly at the oldest age classes. A correction factor was applied to rays and spines that remedied the underageing, but the correction factor was more successful for spines. An analysis of ray and spine section accuracy based on nonlethal structure removal from the fish (i.e., comparing ages from sections at the base of the structure within the body to those sectioned from the external surface of the body) determined that spines can be accurately aged when sampled distal of the base of the structure, but that rays cannot. Nonlethal sampling and ageing of Goliath Grouper spines facilitated by public participation could address management goals and help determine the offshore population age structure. Simultaneously, it could contribute critical data needed for a traditional stock assessment, should such a path be warranted by the recovery or management of the species.

Long-term effects of THC exposure on reward learning and motivated behavior in adolescent and adult male rats - Briac Halbout; Collin Hutson; Leann Hua; Victoria Inshishian; Stephen V. Mahler; Sean B. Ostlund (Psychopharmacology, 2023)
Rationale The endocannabinoid system makes critical contributions to reward processing, motivation, and behavioral control. Repeated exposure to THC or other cannabinoid drugs can cause persistent adaptions in the endocannabinoid system and associated neural circuitry. It remains unclear how such treatments affect the way rewards are processed and pursued. Objective and methods We examined if repeated THC exposure (5 mg/kg/day for 14 days) during adolescence or adulthood led to long-term changes in rats’ capacity to flexibly encode and use action-outcome associations for goal-directed decision making. Effects on hedonic feeding and progressive ratio responding were also assessed. Results THC exposure had no effect on rats’ ability to flexibly select actions following reward devaluation. However, instrumental contingency degradation learning, which involves avoiding an action that is unnecessary for reward delivery, was augmented in rats with a history of adult but not adolescent THC exposure. THC-exposed rats also displayed more vigorous instrumental behavior in this study, suggesting a motivational enhancement. A separate experiment found that while THC exposure had no effect on hedonic feeding behavior, it increased rats’ willingness to work for food on a progressive ratio schedule, an effect that was more pronounced when THC was administered to adults. Adolescent and adult THC exposure had opposing effects on the CB1 receptor dependence of progressive ratio performance, decreasing and increasing sensitivity to rimonabant-induced behavioral suppression, respectively. Conclusions Our findings reveal that exposure to a translationally relevant THC exposure regimen induces long-lasting, age-dependent alterations in cognitive and motivational processes that regulate the pursuit of rewards.

Canine scent detection of sinonasal-inverted papilloma in blood plasma and nasal secretions - Amritha Mallikarjun; Amanda Collins; Alec Verta; Amit Hanadari-Levy; Mark B. Chaskes; Marc R. Rosen; Gurston G. Nyquist; Elina Toskala; Mindy R. Rabinowitz; Cynthia M. Otto (Journal of Veterinary Behavior, 2023)

Hydrologic restoration of anthropoentically altered springs in the Sheldon National Wildlife Refuge in the Great Basin, USA - Leah N. Knighton; Steven L. Petersen; Gail H. Collins; Loreen Allphin; Neil C. Hansen; Haley B. Johnston; Russell B. Rader (Journal of Arid Environments, 2023)

Airborne levels of cadmium are correlated with urinary cadmium concentrations among young children living in the New York state city of Syracuse, USA - Dustin T. Hill; Vikrant Jandev; Michael Petroni; Nader Atallah-Yunes; Kestas Bendinskas; Lynn S. Brann; Kevin Heffernan; David A. Larsen; James A. MacKenzie; Christopher D. Palmer; Patrick J. Parsons; Brooks B. Gump; et al. (Environmental Research, 2023)

Identification of a Female-Produced Sex Attractant Pheromone of the Winter Firefly, Photinus corruscus Linnaeus (Coleoptera: Lampyridae) - Sarah E. Lower; Gregory M. Pask; Kyle Arriola; Sean Halloran; Hannah Holmes; Daphné C. Halley; Yiyu Zheng; Douglas B. Collins; Jocelyn G. Millar (Journal of Chemical Ecology, 2023)
Firefly flashes are well-known visual signals used by these insects to find, identify, and choose mates. However, many firefly species have lost the ability to produce light as adults. These “unlighted” species generally lack developed adult light organs, are diurnal rather than nocturnal, and are believed to use volatile pheromones acting over a distance to locate mates. While cuticular hydrocarbons, which may function in mate recognition at close range, have been examined for a handful of the over 2000 extant firefly species, no volatile pheromone has ever been identified. In this study, using coupled gas chromatography - electroantennographic detection, we detected a single female-emitted compound that elicited antennal responses from wild-caught male winter fireflies, Photinus corruscus . The compound was identified as (1 S )- exo -3-hydroxycamphor (hydroxycamphor). In field trials at two sites across the species’ eastern North American range, large numbers of male P. corruscus were attracted to synthesized hydroxycamphor, verifying its function as a volatile sex attractant pheromone. Males spent more time in contact with lures treated with synthesized hydroxycamphor than those treated with solvent only in laboratory two-choice assays. Further, using single sensillum recordings, we characterized a pheromone-sensitive odorant receptor neuron in a specific olfactory sensillum on male P. corruscus antennae and demonstrated its sensitivity to hydroxycamphor. Thus, this study has identified the first volatile pheromone and its corresponding sensory neuron for any firefly species , and provides a tool for monitoring P. corruscus populations for conservation and further inquiry into the chemical and cellular bases for sexual communication among fireflies.

Understanding heterogeneity of responses to, and optimizing clinical efficacy of, exercise training in older adults: NIH NIA Workshop summary - Melissa L. Erickson; Jacob M. Allen; Daniel P. Beavers; Linda M. Collins; Karina W. Davidson; Kirk I. Erickson; Karyn A. Esser; Matthijs K. C. Hesselink; Kerrie L. Moreau; Eric B. Laber; Charlotte A. Peterson; Courtney M. Peterson; et al. (GeroScience, 2023)
Exercise is a cornerstone of preventive medicine and a promising strategy to intervene on the biology of aging. Variation in the response to exercise is a widely accepted concept that dates back to the 1980s with classic genetic studies identifying sequence variations as modifiers of the VO 2 max response to training. Since that time, the literature of exercise response variance has been populated with retrospective analyses of existing datasets that are limited by a lack of statistical power from technical error of the measurements and small sample sizes, as well as diffuse outcomes, very few of which have included older adults. Prospective studies that are appropriately designed to interrogate exercise response variation in key outcomes identified a priori and inclusive of individuals over the age of 70 are long overdue. Understanding the underlying intrinsic (e.g., genetics and epigenetics) and extrinsic (e.g., medication use, diet, chronic disease) factors that determine robust versus poor responses to various exercise factors will be used to improve exercise prescription to target the pillars of aging and optimize the clinical efficacy of exercise training in older adults. This review summarizes the proceedings of the NIA-sponsored workshop entitled, “Understanding Heterogeneity of Responses to, and Optimizing Clinical Efficacy of, Exercise Training in Older Adults” and highlights the importance and current state of exercise response variation research, particularly in older adults, prevailing challenges, and future directions.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Stronger fertilization effects on aboveground versus belowground plant properties across nine U.S. grasslands - Adrienne B. Keller; Christopher A. Walter; Dana M. Blumenthal; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Johannes M. H. Knops; Andrew D. B. Leakey; Melanie A. Mayes; Eric W. Seabloom; et al. (Ecology, 2023)
Increased nutrient inputs due to anthropogenic activity are expected to increase primary productivity across terrestrial ecosystems, but changes in allocation aboveground versus belowground with nutrient addition have different implications for soil carbon (C) storage. Thus, given that roots are major contributors to soil C storage, understanding belowground net primary productivity (BNPP) and biomass responses to changes in nutrient availability is essential to predicting carbon–climate feedbacks in the context of interacting global environmental changes. To address this knowledge gap, we tested whether a decade of nitrogen (N) and phosphorus (P) fertilization consistently influenced aboveground and belowground biomass and productivity at nine grassland sites spanning a wide range of climatic and edaphic conditions in the continental United States. Fertilization effects were strong aboveground, with both N and P addition stimulating aboveground biomass at nearly all sites (by 30% and 36%, respectively, on average). P addition consistently increased root production (by 15% on average), whereas other belowground responses to fertilization were more variable, ranging from positive to negative across sites. Site‐specific responses to P were not predicted by the measured covariates. Atmospheric N deposition mediated the effect of N fertilization on root biomass and turnover. Specifically, atmospheric N deposition was positively correlated with root turnover rates, and this relationship was amplified with N addition. Nitrogen addition increased root biomass at sites with low N deposition but decreased it at sites with high N deposition. Overall, these results suggest that the effects of nutrient supply on belowground plant properties are context dependent, particularly with regard to background N supply rates, demonstrating that site conditions must be considered when predicting how grassland ecosystems will respond to increased nutrient loading from anthropogenic activity.

Plant defense synergies and antagonisms affect performance of specialist herbivores of common milkweed - Collin B. Edwards; Stephen P. Ellner; Anurag A. Agrawal (Ecology, 2023)
As a general rule, plants defend against herbivores with multiple traits. The defense synergy hypothesis posits that some traits are more effective when co‐expressed with others compared to their independent efficacy. However, this hypothesis has rarely been tested outside of phytochemical mixtures, and seldom under field conditions. We tested for synergies between multiple defense traits of common milkweed ( Asclepias syriaca ) by assaying the performance of two specialist chewing herbivores on plants in natural populations. We employed regression and a novel application of random forests to identify synergies and antagonisms between defense traits. We found the first direct empirical evidence for two previously hypothesized defense synergies in milkweed (latex by secondary metabolites, latex by trichomes) and identified numerous other potential synergies and antagonisms. Our strongest evidence for a defense synergy was between leaf mass per area and low nitrogen content; given that these “leaf economic” traits typically covary in milkweed, a defense synergy could reinforce their co‐expression. We report that each of the plant defense traits showed context‐dependent effects on herbivores, and increased trait expression could well be beneficial to herbivores for some ranges of observed expression. The novel methods and findings presented here complement more mechanistic approaches to the study of plant defense diversity and provide some of the best evidence to date that multiple classes of plant defense synergize in their impact on insects. Plant defense synergies against highly specialized herbivores, as shown here, are consistent with ongoing reciprocal evolution between these antagonists.

Salinity-induced ionoregulatory changes in the gill proteome of the mayfly, Neocloeon triangulifer - Sarah E. Orr; Leonard B. Collins; Dereje D. Jima; David B. Buchwalter (Environmental Pollution, 2023)

Targeted pollution management can significantly reduce toxic emissions while limiting adverse effects on employment in US manufacturing - Mary B. Collins; Simone Pulver; Dustin T. Hill; Ben Manski (Environmental Science & Policy, 2023)

Successful restoration of archived ovine formalin fixed paraffin-embedded tissue DNA and single nucleotide polymorphism analysis - Amanda Kravitz; Ron Tyler; B. Murali Manohar; B. Samuel Masilamoni Ronald; Michael T. Collins; Nammalwar Sriranganathan (Veterinary Research Communications, 2023)
Archived formalin fixed paraffin-embedded (FFPE) tissues are powerful tools in medicine, capable of harboring diagnostic and genetic answers to challenging clinical questions. Successful utilization of DNA derived from FFPE samples is dependent upon repairing DNA damage generated from the fixation process. Methods to repair FFPE DNA have been successful in human medicine for a variety of research and clinical applications, yet remain underutilized in veterinary medicine. Despite the available technology, our study is the first to evaluate the repair of FFPE derived DNA from veterinary species for single-nucleotide polymorphism (SNP) analysis using the Illumina OvineSNP50 BeadChip and Illumina FFPE QC and DNA Restore kit. To accomplish this, 48 ovine FFPE samples were run using the Illumina OvineSNP50 BeadChip with and without restoration. Compared to pre-restore data, we found increased sample call rates, SNP call frequency, and assay metrics for all samples post-restoration. Further, we utilized four sheep with available parallel fresh DNA and FFPE DNA to compare assay metrics and genotype calls between the two starting sample types. Although fresh samples generated increased call rates, we found 99% concordance in allele calls between restored FFPE and fresh DNA for all four samples. Our results indicate successful restoration and genotyping of ovine FFPE samples using this technology, with potential for utilization in other veterinary species.

Soil CO2 emissions in cropland with fodder maize (Zea mays L.) with and without riparian buffer strips of differing vegetation - J. C. Dlamini; L. M. Cardenas; E. H. Tesfamariam; R. M. Dunn; J. Evans; J. M. B. Hawkins; M. S. A. Blackwell; A. L. Collins (Agroforestry Systems, 2022)
Vegetated land areas play a significant role in determining the fate of carbon (C) in the global C cycle. Riparian buffer vegetation is primarily implemented for water quality purposes as they attenuate pollutants from immediately adjacent croplands before reaching freashwater systems. However, their prevailing conditions may sometimes promote the production and subsequent emissions of soil carbon dioxide (CO 2 ). Despite this, the understanding of soil CO 2 emissions from riparian buffer vegetation and a direct comparison with adjacent croplands they serve remain elusive. In order to quantify the extent of CO 2 emissions in such an agro system, we measured CO 2 emissions simultaneously with soil and environmental variables for six months in a replicated plot-scale facility comprising of maize cropping served by three vegetated riparian buffers, namely: (i) a novel grass riparian buffer; (ii) a willow riparian buffer, and; (iii) a woodland riparian buffer. These buffered treatments were compared with a no-buffer control. The woodland (322.9 ± 3.1 kg ha − 1 ) and grass (285 ± 2.7 kg ha − 1 ) riparian buffer treatments (not significant to each other) generated significantly ( p = ) the largest CO 2 compared to the remainder of the treatments. Our results suggest that during maize production in general, the woodland and grass riparian buffers serving a maize crop pose a CO 2 threat. The results of the current study point to the need to consider the benefits for gaseous emissions of mitigation measures conventionally implemented for improving the sustainability of water resources.

Assessing the quantity and toxicity of chemical releases from TRI facilities in Upstate New York - Amanda T. Charette; Dustin T. Hill; Mary B. Collins; Jaime E. Mirowsky (Journal of Environmental Studies and Sciences, 2022)

Soil N2O and CH4 emissions from fodder maize production with and without riparian buffer strips of differing vegetation - Jerry C. Dlamini; L. M. Cardenas; E. H. Tesfamariam; R. M. Dunn; J. Evans; J. M. B. Hawkins; M. S. A. Blackwell; A. L. Collins (Plant and Soil, 2022)
Purpose Nitrous oxide (N 2 O) and methane (CH 4 ) are some of the most important greenhouse gases in the atmosphere of the 21st century. Vegetated riparian buffers are primarily implemented for their water quality functions in agroecosystems. Their location in agricultural landscapes allows them to intercept and process pollutants from adjacent agricultural land. They recycle organic matter, which increases soil carbon (C), intercept nitrogen (N)-rich runoff from adjacent croplands, and are seasonally anoxic. Thus processes producing environmentally harmful gases including N 2 O and CH 4 are promoted. Against this context, the study quantified atmospheric losses between a cropland and vegetated riparian buffers that serve it. Methods Environmental variables and simultaneous N 2 O and CH 4 emissions were measured for a 6-month period in a replicated plot-scale facility comprising maize ( Zea mays L.). A static chamber was used to measure gas emissions. The cropping was served by three vegetated riparian buffers, namely: (i) grass riparian buffer; (ii) willow riparian buffer and; (iii) woodland riparian buffer, which were compared with a no-buffer control. Results The no-buffer control generated the largest cumulative N 2 O emissions of 18.9 kg ha − 1 (95% confidence interval: 0.5–63.6) whilst the maize crop upslope generated the largest cumulative CH 4 emissions (5.1 ± 0.88 kg ha − 1 ). Soil N 2 O and CH 4 -based global warming potential (GWP) were lower in the willow (1223.5 ± 362.0 and 134.7 ± 74.0 kg CO 2 -eq. ha − 1 year − 1 , respectively) and woodland (1771.3 ± 800.5 and 3.4 ± 35.9 kg CO 2 -eq. ha − 1 year − 1 , respectively) riparian buffers. Conclusions Our results suggest that in maize production and where no riparian buffer vegetation is introduced for water quality purposes (no buffer control), atmospheric CH 4 and N 2 O concerns may result.

Short-Term Response of Deep-Water Benthic Megafauna to Installation of a Pipeline Over a Depth Gradient on the Angolan Slope - Virginia Biede; Andrew R. Gates; Simone Pfeifer; Jane E. Collins; Carmen Santos; Daniel O. B. Jones (Frontiers in Marine Science, 2022)
Large structures are introduced into deep-water marine environments by several industrial activities, including hydrocarbon exploitation. Anthropogenic structures can alter ecosystem structure and functioning in many marine ecosystems but the responses on continental margins are poorly known. Here, we investigate the short-term response of benthic megafauna to the installation of a 56 km-long 30 cm diameter pipeline on the Angolan Margin (Block 31) from 700 to 1800 m water depth using remotely operated vehicle imagery. Clear depth-related patterns exist in the density, diversity and community structure of megafauna observed in 2013 prior to pipeline installation. These patterns are altered in a subsequent survey in 2014, three-months after pipeline installation. Significant increases in density, particularly in mid-slope regions are observed. Diversity is generally, but not consistently, enhanced, particularly in the shallower areas in 2014. Clear changes are noted in community structure between years. These changes are primarily caused by increases in the abundance of echinoderms, particularly the echinoid Phormosoma sp. indet. There was no evidence of colonisation of the pipeline in three months by visible fauna. The few large anemones observed attached to the pipe may be able to move as adults. The pipeline appeared to trap organic material and anthropogenic litter, and may enhance available food resources locally as well as providing hard substratum. These results indicate complex and ecosystem-dependent responses to structure installation and caution against simplistic approaches to environmental management.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Using structured decision making to guide habitat restoration for butterflies: a case study of Oregon silverspots - Cassandra F. Doll; Sarah J. Converse; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2022)

Widespread Use of Migratory Megafauna for Aquatic Wild Meat in the Tropics and Subtropics - Daniel J. Ingram; Margi Prideaux; Nicola K. Hodgins; Heidrun Frisch-Nwakanma; Isabel C. Avila; Tim Collins; Mel Cosentino; Lucy W. Keith-Diagne; Helene Marsh; Matthew H. Shirley; Koen Van Waerebeek; Maximin K. Djondo; et al. (Frontiers in Marine Science, 2022)
Wild animals are captured or taken opportunistically, and the meat, body parts, and/or eggs are consumed for local subsistence or used for traditional purposes to some extent across most of the world, particularly in the tropics and subtropics. The consumption of aquatic animals is widespread, in some places has been sustained for millennia, and can be an important source of nutrition, income, and cultural identity to communities. Yet, economic opportunities to exploit wildlife at higher levels have led to unsustainable exploitation of some species. In the literature, there has been limited focus on the exploitation of aquatic non-fish animals for food and other purposes. Understanding the scope and potential threat of aquatic wild meat exploitation is an important first step toward appropriate inclusion on the international policy and conservation management agenda. Here, we conduct a review of the literature, and present an overview of the contemporary use of aquatic megafauna (cetaceans, sirenians, chelonians, and crocodylians) in the global tropics and subtropics, for species listed on the Appendices of the Convention on the Conservation of Migratory Species of Wild Animals (CMS). We find that consumption of aquatic megafauna is widespread in coastal regions, although to varying degrees, and that some species are likely to be at risk from overexploitation, particularly riverine megafauna. Finally, we provide recommendations for CMS in the context of the mandate of the Aquatic Wild Meat Working Group.

Zooplankton Abundance Reflects Oxygen Concentration and Dissolved Organic Matter in a Seasonally Hypoxic Estuary - Jane B. Weinstock; Lourdes Vargas; Rachel Collin (Journal of Marine Science and Engineering, 2022)
Ocean deoxygenation, warming, and acidification resulting from global change and increasing nutrient inputs are major threats to marine ecosystems. Despite this, spatial and temporal patterns of oxygen availability and their impacts on marine life are understudied compared to warming and acidification, particularly in coastal tropical ecosystems. We measured the abundance of major groups of zooplankton in the context of five covarying environmental parameters [temperature, salinity, dissolved oxygen (DO), dissolved organic matter (DOM), and chlorophyll concentration] in a tropical estuary for one year. Partial least squares demonstrated that environmental conditions explained 20% of the variation in the community and found that temperature, salinity, DO, and DOM were most important (Variable Importance in Projection [VIP] > 0.8). A generalized linear model identified depth, DO, salinity, and chlorophyll as significant main effects, and temperature and DOM were also significant via two-way interactions (p

Mercury exposure of tidal marsh songbirds in the northeastern United States and its association with nest survival - Katharine J. Ruskin; Garth Herring; Collin A. Eagles-Smith; Alyssa B. Eiklor; Chris S. Elphick; Matthew A. Etterson; Christopher R. Field; Rebecca A. Longenecker; Adrienne I. Kovach; W. Gregory Shriver; Jennifer Walsh; Brian J. Olsen (Ecotoxicology, 2022)

Soil carbon stocks in temperate grasslands differ strongly across sites but are insensitive to decade‐long fertilization - Adrienne B. Keller; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Andrew D.B. Leakey; Melanie A. Mayes; Eric W. Seabloom; Christopher A. Walter; Yong Wang; Qian Zhao; et al. (Global Change Biology, 2022)
Enhancing soil carbon (C) storage has the potential to offset human‐caused increases in atmospheric CO 2 . Rising CO 2 has occurred concurrently with increasing supply rates of biologically limiting nutrients such as nitrogen (N) and phosphorus (P). However, it is unclear how increased supplies of N and P will alter soil C sequestration, particularly in grasslands, which make up nearly a third of non‐agricultural land worldwide. Here, we leverage a globally distributed nutrient addition experiment (the Nutrient Network) to examine how a decade of N and P fertilization (alone and in combination) influenced soil C and N stocks at nine grassland sites spanning the continental United States. We measured changes in bulk soil C and N stocks and in three soil C fractions (light and heavy particulate organic matter, and mineral‐associated organic matter fractions). Nutrient amendment had variable effects on soil C and N pools that ranged from strongly positive to strongly negative, while soil C and N pool sizes varied by more than an order of magnitude across sites. Piecewise SEM clarified that small increases in plant C inputs with fertilization did not translate to greater soil C storage. Nevertheless, peak season aboveground plant biomass (but not root biomass or production) was strongly positively related to soil C storage at seven of the nine sites, and across all nine sites, soil C covaried with moisture index and soil mineralogy, regardless of fertilization. Overall, we show that site factors such as moisture index, plant productivity, soil texture, and mineralogy were key predictors of cross‐site soil C, while nutrient amendment had weaker and site‐specific effects on C sequestration. This suggests that prioritizing the protection of highly productive temperate grasslands is critical for reducing future greenhouse gas losses arising from land use change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Hydrological sentinels and the relative emergence of climate change signals in New Zealand river flows - Daniel B. G. Collins (Hydrological Sciences Journal, 2021)

Biogeochemical status of the Paleo-Pacific Ocean: clues from the early Cambrian of South Australia - P. A. Hall; D. M. McKirdy; G. P. Halverson; J. B. Jago; A. S. Collins (Australian Journal of Earth Sciences, 2021)

When hazard avoidance is not an option: lessons learned from monitoring the postdisaster Oso landslide, USA - Mark E. Reid; Jonathan W. Godt; Richard G. LaHusen; Stephen L. Slaughter; Thomas C. Badger; Brian D. Collins; William H. Schulz; Rex L. Baum; Jeffrey A. Coe; Edwin L. Harp; Kevin M. Schmidt; Richard M. Iverson; et al. (Landslides, 2021)
On 22 March 2014, a massive, catastrophic landslide occurred near Oso, Washington, USA, sweeping more than 1 km across the adjacent valley flats and killing 43 people. For the following 5 weeks, hundreds of workers engaged in an exhaustive search, rescue, and recovery effort directly in the landslide runout path. These workers could not avoid the risks posed by additional large-scale slope collapses. In an effort to ensure worker safety, multiple agencies cooperated to swiftly deploy a monitoring and alerting system consisting of sensors, automated data processing and web-based display, along with defined communication protocols and clear calls to action for emergency management and search personnel. Guided by the principle that an accelerating landslide poses a greater threat than a steadily moving or stationary mass, the system was designed to detect ground motion and vibration using complementary monitoring techniques. Near real-time information was provided by continuous GPS, seismometers/geophones, and extensometers. This information was augmented by repeat-assessment techniques such as terrestrial and aerial laser scanning and time-lapse photography. Fortunately, no major additional landsliding occurred. However, we did detect small headscarp failures as well as slow movement of the remaining landslide mass with the monitoring system. This was an exceptional response situation and the lessons learned are applicable to other landslide disaster crises. They underscore the need for cogent landslide expertise and ready-to-deploy monitoring equipment, the value of using redundant monitoring techniques with distinct goals, the benefit of clearly defined communication protocols, and the importance of continued research into forecasting landslide behavior to allow timely warning.

Pyrosilviculture Needed for Landscape Resilience of Dry Western United States Forests - M P North; R A York; B M Collins; M D Hurteau; G M Jones; E E Knapp; L Kobziar; H McCann; M D Meyer; S L Stephens; R E Tompkins; C L Tubbesing (Journal of Forestry, 2021)
A significant increase in treatment pace and scale is needed to restore dry western US forest resilience owing to increasingly frequent and severe wildfire and drought. We propose a pyrosilviculture approach to directly increase large-scale fire use and modify current thinning treatments to optimize future fire incorporation. Recommendations include leveraging wildfire’s “treatment” in areas burned at low and moderate severity with subsequent pyrosilviculture management, identifying managed wildfire zones, and facilitating and financing prescribed fire with “anchor,” “ecosystem asset,” and “revenue” focused thinning treatments. Pyrosilviculture would also expand prescribed-burn and managed-wildfire objectives to include reducing stand density, increasing forest heterogeneity, and selecting for tree species and phenotypes better adapted to changing climate and disturbance regimes. The potential benefits and limitations of this approach are discussed. Fire is inevitable in dry western US forests and pyrosilviculture focuses on proactively shifting more of that fire into managed large-scale burns needed to restore ecosystem resilience.

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Changes in phenology and abundance of an at-risk butterfly - Rachael E. Bonoan; Elizabeth E. Crone; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2021)

Correction to: Neotype designation and re-description of Forsskål’s reticulate whipray Himantura uarnak - Philippe Borsa; Collin T. Williams; Ashlie J. McIvor; Thierry B. Hoareau; Michael L. Berumen (Marine Biodiversity, 2021)

Assessing residential socioeconomic factors associated with pollutant releases using EPA’s Toxic Release Inventory - Amanda T. Charette; Mary B. Collins; Jaime E. Mirowsky (Journal of Environmental Studies and Sciences, 2021)

Understanding Persistent Non-compliance in a Remote, Large-Scale Marine Protected Area - Claire Collins; Ana Nuno; Annette Broderick; David J. Curnick; Asha de Vos; Thomas Franklin; David M. P. Jacoby; Chris Mees; James Moir-Clark; John Pearce; Tom B. Letessier (Frontiers in Marine Science, 2021)
Area coverage of large-scale marine protected areas (MPAs) (LSMPAs, > 100,000 km 2 ) is rapidly increasing globally. Their effectiveness largely depends on successful detection and management of non-compliance. However, for LSMPAs this can be difficult due to their large size, often remote locations and a lack of understanding of the social drivers of non-compliance. Taking a case-study approach, we review current knowledge of illegal fishing within the British Indian Ocean Territory (BIOT) LSMPA. Data stemming from enforcement reports (2010–20), and from fieldwork in fishing communities (2018–19) were combined to explore and characterise drivers of non-compliance. Enforcement data included vessel investigation reports ( n = 188), transcripts of arrests (20) and catch seizures (58). Fieldwork data included fisher interviews (95) and focus groups (12), conducted in two communities in Sri Lanka previously associated with non-compliance in BIOT LSMPA. From 2010 to 2020, there were 126 vessels suspected of non-compliance, 76% of which were Sri Lankan. The majority of non-compliant vessels targeted sharks (97%), catching an estimated 14,340 individuals during the study period. Sri Lankan vessels were primarily registered to one district (77%) and 85% operated from just two ports within the fieldwork sites. Social Network Analysis (SNA) showed that 66% of non-compliant vessels were linked by social ties, including sharing crew members, compared with only 34% of compliant vessels. Thematic analysis of qualitative data suggested that perceptions of higher populations of sharks and social ties between vessels may both be important drivers. We discuss our findings within a global context to identify potential solutions for LSMPA management.

Scale‐dependent signatures of local adaptation in a foundation tree species - Brenton von Takach; Collin W. Ahrens; David B. Lindenmayer; Sam C. Banks (Molecular Ecology, 2021)
Understanding local adaptation is critical for conservation management under rapidly changing environmental conditions. Local adaptation inferred from genotype‐environment associations may show different genomic patterns depending on the spatial scale of sampling, due to differences in the slope of environmental gradients and the level of gene flow. We compared signatures of local adaptation across the genome of mountain ash ( Eucalyptus regnans ) at two spatial scales: A species‐wide data set and a topographically‐complex subregional data set. We genotyped 367 individual trees at over 3700 single‐nucleotide polymorphisms (SNPs), quantified patterns of spatial genetic structure among populations, and used two analytical methods to identify loci associated with at least one of three environmental variables at each spatial scale. Together, the analyses identified 549 potentially adaptive SNPs at the subregion scale, and 435 SNPs at the range‐wide scale. A total of 39 genic or near‐genic SNPs, associated with 28 genes, were identified at both spatial scales, although no SNP was identified by both methods at both scales. We observed that nongenic regions had significantly higher homozygote excess than genic regions, possibly due to selective elimination of inbred genotypes during stand development. Our results suggest that strong environmental selection occurs in mountain ash, and that the identification of putatively adaptive loci can differ substantially depending on the spatial scale of analyses. We also highlight the importance of multiple adaptive genetic architectures for understanding patterns of local adaptation across large heterogenous landscapes, with comparison of putatively adaptive loci among spatial scales providing crucial insights into the process of adaptation.

Neotype designation and re-description of Forsskål’s reticulate whipray Himantura uarnak - Philippe Borsa; Collin T. Williams; Ashlie J. McIvor; Thierry B. Hoareau; Michael L. Berumen (Marine Biodiversity, 2021)

Negative impacts of invasive predators used as biological control agents against the pest snail Lissachatina fulica: the snail Euglandina ‘rosea’ and the flatworm Platydemus manokwari - Justin Gerlach; Gary M. Barker; Cindy S. Bick; Philippe Bouchet; Gilianne Brodie; Carl C. Christensen; Timothy Collins; Trevor Coote; Robert H. Cowie; G. Curt Fiedler; Owen L. Griffiths; F. B. Vincent Florens; et al. (Biological Invasions, 2021)
Since 1955 snails of the Euglandina rosea species complex and Platydemus manokwari flatworms were widely introduced in attempted biological control of giant African snails ( Lissachatina fulica ) but have been implicated in the mass extinction of Pacific island snails. We review the histories of the 60 introductions and their impacts on L. fulica and native snails. Since 1993 there have been unofficial releases of Euglandina within island groups. Only three official P. manokwari releases took place, but new populations are being recorded at an increasing rate, probably because of accidental introduction. Claims that these predators controlled L. fulica cannot be substantiated; in some cases pest snail declines coincided with predator arrival but concomitant declines occurred elsewhere in the absence of the predator and the declines in some cases were only temporary. In the Hawaiian Islands, although there had been some earlier declines of native snails, the Euglandina impacts on native snails are clear with rapid decline of many endemic Hawaiian Achatinellinae following predator arrival. In the Society Islands, Partulidae tree snail populations remained stable until Euglandina introduction, when declines were extremely rapid with an exact correspondence between predator arrival and tree snail decline. Platydemus manokwari invasion coincides with native snail declines on some islands, notably the Ogasawara Islands of Japan, and its invasion of Florida has led to mass mortality of Liguus spp. tree snails. We conclude that Euglandina and P. manokwari are not effective biocontrol agents, but do have major negative effects on native snail faunas. These predatory snails and flatworms are generalist predators and as such are not suitable for biological control.

Environmental heterogeneity predicts global species richness patterns better than area - Kristy Udy; Matthias Fritsch; Katrin M. Meyer; Ingo Grass; Sebastian Hanß; Florian Hartig; Thomas Kneib; Holger Kreft; Collins B. Kukunda; Guy Pe’er; Hannah Reininghaus; Britta Tietjen; et al. (Global Ecology and Biogeography, 2021)
Aim It is widely accepted that biodiversity is influenced by both niche‐related and spatial processes from local to global scales. Their relative importance, however, is still disputed, and empirical tests are surprisingly scarce at the global scale. Here, we compare the importance of area (as a proxy for pure spatial processes) and environmental heterogeneity (as a proxy for niche‐related processes) for predicting native mammal species richness world‐wide and within biogeographical regions. Location Global. Time period We analyse a spatial snapshot of richness data collated by the International Union for Conservation of Nature. Major taxa studied All terrestrial mammal species, including possibly extinct species and species with uncertain presence. Methods We applied a spreading dye algorithm to analyse how native mammal species richness changes with area and environmental heterogeneity. As measures for environmental heterogeneity, we used elevation ranges and precipitation ranges, which are well‐known correlates of species richness. Results We found that environmental heterogeneity explained species richness relationships better than did area, suggesting that niche‐related processes are more prevalent than pure area effects at broad scales. Main conclusions Our results imply that niche‐related processes are essential to understand broad‐scale species–area relationships and that habitat diversity is more important than area alone for the protection of global biodiversity.

Fire frequency, state change and hysteresis in tallgrass prairie - Scott L. Collins; Jesse B. Nippert; John M. Blair; John M. Briggs; Pamela Blackmore; Zak Ratajczak (Ecology Letters, 2021)
Hysteresis is a fundamental characteristic of alternative stable state theory, yet evidence of hysteresis is rare. In mesic grasslands, fire frequency regulates transition from grass‐ to shrub‐dominated system states. It is uncertain, however, if increasing fire frequency can reverse shrub expansion, or if grass‐shrub dynamics exhibit hysteresis. We implemented annual burning in two infrequently burned grasslands and ceased burning in two grasslands burned annually. With annual fires, grassland composition converged on that of long‐term annually burned vegetation due to rapid recovery of grass cover, although shrubs persisted. When annual burning ceased, shrub cover increased, but community composition did not converge with a long‐term infrequently burned reference site because of stochastic and lagged dispersal by shrubs, reflecting hysteresis. Our results demonstrated that annual burning can slow, but not reverse, shrub encroachment. In addition, reversing fire frequencies resulted in hysteresis because vegetation trajectories from grassland to shrubland differed from those of shrubland to grassland.

Life History and Ecology of Bluenose Warehou (Hyperoglyphe antarctica, Centrolophidae) in the Southern Atlantic - James B. Bell; Vladimir Laptikhovsky; David K. A. Barnes; Ramon Benedet; Amelia E. Bridges; James Glass; Warren Glass; Rodney Green; Simon A. Morley; Simon Robertson; Georgia R. Robson; Harry Stanton; et al. (Frontiers in Marine Science, 2021)
Bluenose warehou ( Hyperoglyphe antarctica ) is a popular commercial fish in Australia and New Zealand, but its biology and ecology are very poorly known in other regions where it is found. We present here the first life history data for this species from the south Atlantic, focusing upon the exclusive economic zone (EEZ) of the United Kingdom Overseas Territory (UKOT) of Tristan da Cunha (TdC). Here, bluenose is known from several seamounts and island margins, typically occurring in waters between 200 and 1,000 m depth and is the target species of trawl and longline fishery operating since 1997. We use a suite of methods to describe important life history parameters, including length-weight and age-length relationships and size at recruitment, as well as examining commercial longline survey data to uncover habitat preferences of bluenose. This work has formed an important part of the United Kingdom government’s Blue Belt Program in TdC. It has underpinned the development of the first stock assessment for this species in the Atlantic, as well as a range of improved conservation measures for some of the more vulnerable species that occur in these areas, including seabirds and cold-water corals.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Modern pollen assemblages of the Neotropics - Mark B. Bush; Alex Correa‐Metrio; Robert van Woesik; Aaron Collins; Jennifer Hanselman; Pablo Martinez; Crystal N. H. McMichael (Journal of Biogeography, 2021)
Aim Modern pollen assemblages provide a means to calibrate fossil pollen data and to provide a translation from habitat and vegetation type to pollen representation. Here we provide a database of modern pollen abundances from a broad range of neotropical habitats and locations. Location The Neotropics, especially western Amazonia, the Andes, The Galápagos, Central America, Puerto Rico and Mexico. Taxon Angiosperms and Gymnosperms Methods Over a 30‐year period, mud–water interface samples, moss polsters, soils and pollen traps were used to assay modern pollen assemblages. Standard extraction methods were used, and a minimum of 300 terrestrial pollen grains were counted and identified in each sample. Bioclimatic data were assigned to each location, and sexual traits and pollination syndromes are provided for some genera. A detrended correspondence analysis (DCA) shows the structuring of the data relative to mean annual temperatures (MAT), mean annual precipitation (MAP) and precipitation of the driest quarter (PDQ). Probability density functions of distances among samples are calculated within and between Holdridge Life Zones, based on sample DCA scores. Results The modern pollen of 636 locations are documented, with >500 pollen types identified. The dataset spans settings with MAT 25°C, and with MAP ranging from c. 500 to 5,000 mm, and PDQ from 80 to 1,500 mm. Ordination of the dataset provides evidence that assemblages differ according to temperature and precipitation, although historical biogeography also shapes pollen rains. The pollen grains of zoophilous species contribute important information to habitat descriptions, but they are under‐represented in the dataset. Main conclusions The dataset covers a broad environmental range and can help inform biogeographical and palaeoenvironmental interpretation of palaeoecological records. Some caution in using the data is needed as the field of tropical palynology is maturing and the data gathered 30 years ago are less detailed than those gathered recently. Although anemophilous taxa tend to be over‐represented in neotropical pollen spectra, the majority of pollen identified in each sample are from zoophilous species.

Temporal variability in production is not consistently affected by global change drivers across herbaceous-dominated ecosystems - Meghan L. Avolio; Kevin R. Wilcox; Kimberly J. Komatsu; Nathan Lemoine; William D. Bowman; Scott L. Collins; Alan K. Knapp; Sally E. Koerner; Melinda D. Smith; Sara G. Baer; Katherine L. Gross; Forest Isbell; et al. (Oecologia, 2020)

Belowground impacts of alpine woody encroachment are determined by plant traits, local climate, and soil conditions - Courtney G. Collins; Marko J. Spasojevic; Concepción L. Alados; Emma L. Aronson; Juan C. Benavides; Nicoletta Cannone; Chatrina Caviezel; Oriol Grau; Hui Guo; Gaku Kudo; Nikolas J. Kuhn; Jana Müllerová; et al. (Global Change Biology, 2020)
Global climate and land use change are causing woody plant encroachment in arctic, alpine, and arid/semi‐arid ecosystems around the world, yet our understanding of the belowground impacts of this phenomenon is limited. We conducted a globally distributed field study of 13 alpine sites across four continents undergoing woody plant encroachment and sampled soils from both woody encroached and nearby herbaceous plant community types. We found that woody plant encroachment influenced soil microbial richness and community composition across sites based on multiple factors including woody plant traits, site level climate, and abiotic soil conditions. In particular, root symbiont type was a key determinant of belowground effects, as Nitrogen‐fixing woody plants had higher soil fungal richness, while Ecto/Ericoid mycorrhizal species had higher soil bacterial richness and symbiont types had distinct soil microbial community composition. Woody plant leaf traits indirectly influenced soil microbes through their impact on soil abiotic conditions, primarily soil pH and C:N ratios. Finally, site‐level climate affected the overall magnitude and direction of woody plant influence, as soil fungal and bacterial richness were either higher or lower in woody encroached versus herbaceous soils depending on mean annual temperature and precipitation. All together, these results document global impacts of woody plant encroachment on soil microbial communities, but highlight that multiple biotic and abiotic pathways must be considered to scale up globally from site‐ and species‐level patterns. Considering both the aboveground and belowground effects of woody encroachment will be critical to predict future changes in alpine ecosystem structure and function and subsequent feedbacks to the global climate system.

Extended Pelagic Life in a Bathybenthic Octopus - Roger Villanueva; Vladimir V. Laptikhovsky; Stuart B. Piertney; Fernando Ángel Fernández-Álvarez; Martin A. Collins; Jonathan D. Ablett; Alejandro Escánez (Frontiers in Marine Science, 2020)
Planktonic stages of benthic octopuses can reach relatively large sizes in some species, usually in oceanic, epipelagic waters while living as part of the macroplankton. These young octopuses appear to delay settlement on the seabed for an undetermined period of time that is probably longer than for those octopus paralarvae living in coastal, neritic waters. The reason for this delay is unknown and existing information about their biology is very scarce. Here we report on the presence of juvenile and subadult forms of the bathybenthic octopus Pteroctopus tetracirrhus in oceanic waters of the South and North Atlantic and its association with the pyrosomid species Pyrosoma atlanticum , apparently used by the octopus as a refuge or shelter. The relatively large size of the P. tetracirrhus living in oceanic waters as the individuals reported here, together with the morphological characteristics of this bathybenthic species including its gelatinous body, minute suckers embedded in swollen skin and the deep interbrachial web, indicates that P. tetracirrhus may be considered a model of a transitional octopus species that is colonizing the pelagic environment by avoiding descending to the bathyal benthos. This process seems to occur in the same way as in the supposed origin of the ctenoglossan holopelagic octopods of the families Amphitretidae, Bolitaenidae, and Vitreledonellidae, which have arisen via neoteny from the planktonic paralarval stages of benthic octopuses.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Avian haemosporidian prevalence and its relationship to host traits in Western Tennessee - Maria Popescu; Mitch R. Trychta; Emma G. Jackson; John B. Selman; Allan E. Houston; Michael D. Collins (Journal of Ornithology, 2020)

Public money and private interests: United States government contract awardees’ contribution to industrial pollution production - Dustin T. Hill; Elizabeth S. Vidon; Mary B. Collins (Journal of Environmental Studies and Sciences, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Marine Vertebrate Biodiversity and Distribution Within the Central California Current Using Environmental DNA (eDNA) Metabarcoding and Ecosystem Surveys - Collin J. Closek; Jarrod A. Santora; Hilary A. Starks; Isaac D. Schroeder; Elizabeth A. Andruszkiewicz; Keith M. Sakuma; Steven J. Bograd; Elliott L. Hazen; John C. Field; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

Relaxation Response of Critically Stressed Macroscale Surficial Rock Sheets - B. D. Collins; G. M. Stock; M. C. Eppes (Rock Mechanics and Rock Engineering, 2019)

Contaminant Concentrations in Sediments, Aquatic Invertebrates, and Fish in Proximity to Rail Tracks Used for Coal Transport in the Pacific Northwest (USA): A Baseline Assessment - Whitney B. Hapke; Robert W. Black; Collin A. Eagles-Smith; Cassandra D. Smith; Lyndal Johnson; Gina M. Ylitalo; Daryle Boyd; Jay W. Davis; Sara L. Caldwell Eldridge; Elena B. Nilsen (Archives of Environmental Contamination and Toxicology, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Avian host composition, local speciation and dispersal drive the regional assembly of avian malaria parasites in South American birds - Alan Fecchio; Jeffrey A. Bell; Rafael B.P. Pinheiro; Victor R. Cueto; Cristian A. Gorosito; Holly L. Lutz; Milene G. Gaiotti; Luciana V. Paiva; Leonardo F. França; Guilherme Toledo‐Lima; Mariana Tolentino; João B. Pinho; et al. (Molecular Ecology, 2019)
Identifying the ecological factors that shape parasite distributions remains a central goal in disease ecology. These factors include dispersal capability, environmental filters and geographic distance. Using 520 haemosporidian parasite genetic lineages recovered from 7,534 birds sampled across tropical and temperate South America, we tested (a) the latitudinal diversity gradient hypothesis and (b) the distance–decay relationship (decreasing proportion of shared species between communities with increasing geographic distance) for this host–parasite system. We then inferred the biogeographic processes influencing the diversity and distributions of this cosmopolitan group of parasites across South America. We found support for a latitudinal gradient in diversity for avian haemosporidian parasites, potentially mediated through higher avian host diversity towards the equator. Parasite similarity was correlated with climate similarity, geographic distance and host composition. Local diversification in Amazonian lineages followed by dispersal was the most frequent biogeographic events reconstructed for haemosporidian parasites. Combining macroecological patterns and biogeographic processes, our study reveals that haemosporidian parasites are capable of circumventing geographic barriers and dispersing across biomes, although constrained by environmental filtering. The contemporary diversity and distributions of haemosporidian parasites are mainly driven by historical (speciation) and ecological (dispersal) processes, whereas the parasite community assembly is largely governed by host composition and to a lesser extent by environmental conditions.

Integrating national Red Lists for prioritising conservation actions for European butterflies - Dirk Maes; Rudi Verovnik; Martin Wiemers; Dimitri Brosens; Stoyan Beshkov; Simona Bonelli; Jaroslaw Buszko; Lisette Cantú-Salazar; Louis-Francis Cassar; Sue Collins; Vlad Dincă; Milan Djuric; et al. (Journal of Insect Conservation, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A unified framework for land cover monitoring based on a discrete global sampling grid (GSG) - Lutz Fehrmann; Collins B. Kukunda; Nils Nölke; Sebastian Schnell; Dominik Seidel; Steen Magnussen; Christoph Kleinn (Environmental Monitoring and Assessment, 2019)

Aggregating fields of annual crops to form larger-scale monocultures can suppress dispersal-limited herbivores - Collin B. Edwards; Jay A. Rosenheim; Moran Segoli (Theoretical Ecology, 2018)

Inter-Annual Precipitation Variability Decreases Switchgrass Productivity from Arid to Mesic Environments - Lara G. Reichmann; Harold P. Collins; Virginia L. Jin; Mari-Vaughn V. Johnson; Jim R. Kiniry; Robert B. Mitchell; H. Wayne Polley; Philip A. Fay (BioEnergy Research, 2018)

The physiology of saltwater acclimation in large juvenile Atlantic salmon Salmo salar - Morgan S. Brown; Paul L. Jones; Jared J. Tromp; Christian A. van Rijn; Robert A. Collins; Luis O. B. Afonso (Journal of Fish Biology, 2018)
The present study investigated the effects of transferring freshwater (FW) acclimated S. salar (678 g) that had been maintained under a constant photoperiod and thermal regime, into FW (salinity 0) and salt water (SW; salinity 35) on growth and physiological responses over a 28 day period. There were no mortalities observed throughout the study and no significant differences in mass or fork length between FW and SW groups after 28 days. Compared with fish transferred to FW, plasma osmolality and plasma chloride levels increased significantly in fish in SW by day 1. In the SW group, plasma chloride and osmolality had decreased significantly at day 14 when compared with day 1. Na + –K + ‐ATPase activity was significantly higher in SW compared with the FW group from day 7 and thereafter, but continued to increase until day 22. No differences in plasma cortisol and thyroxine were observed between FW and SW groups throughout the study. Plasma glucose significantly increased from day 1 to day 2 in SW but not in the FW group and levels were significantly reduced in SW compared with the FW group at day 28. Plasma cholesterol and triglyceride levels were significantly higher in FW at day 22 and day 14 to day 22, respectively, when compared with the SW group. In the SW group, plasma cholesterol and triglyceride levels did not change significantly throughout the study. The findings of this study suggest that large S. salar retained in FW maintain a high level of SW tolerance in the absence of photoperiod and thermal regimes necessary for smoltification, as demonstrated by 100% survival, unaffected growth performance, increased Na + –K + ‐ATPase activity and a capacity to regulate plasma chloride and osmolality for 28 days in the SW group.

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Variability in soil-water retention properties and implications for physics-based simulation of landslide early warning criteria - Matthew A. Thomas; Benjamin B. Mirus; Brian D. Collins; Ning Lu; Jonathan W. Godt (Landslides, 2018)

A tutorial on model informed approaches to cardiovascular safety with focus on cardiac repolarisation - S. Y. A. Cheung; J. Parkinson; U. Wählby-Hamrén; C. D. Dota; Å. M. Kragh; L. Bergenholm; T. Vik; T. Collins; C. Arfvidsson; C. E. Pollard; H. K. Tomkinson; B. Hamrén (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

Assessing rockfall susceptibility in steep and overhanging slopes using three-dimensional analysis of failure mechanisms - B. Matasci; G. M. Stock; M. Jaboyedoff; D. Carrea; B. D. Collins; A. Guérin; G. Matasci; L. Ravanel (Landslides, 2018)

Flowering in grassland predicted by CO 2 and resource effects on species aboveground biomass - Philip A. Fay; Michael J. Aspinwall; Harold P. Collins; Anne E. Gibson; Richard H. Gill; Robert B. Jackson; Virginia L. Jin; Albina R. Khasanova; Lara G. Reichmann; H. Wayne Polley (Global Change Biology, 2018)
Continuing enrichment of atmospheric CO 2 may change plant community composition, in part by altering the availability of other limiting resources including soil water, nutrients, or light. The combined effects of CO 2 enrichment and altered resource availability on species flowering remain poorly understood. We quantified flowering culm and ramet production and biomass allocation to flowering culms/ramets for 10 years in C 4 ‐dominated grassland communities on contrasting soils along a CO 2 concentration gradient spanning pre‐industrial to expected mid‐21st century levels (250–500 μl/L). CO 2 enrichment explained up to 77% of the variation in flowering culm count across soils for three of the five species, and was correlated with flowering culm count on at least one soil for four of five species. In contrast, allocation to flowering culms was only weakly correlated with CO 2 enrichment for two species. Flowering culm counts were strongly correlated with species aboveground biomass (AGB; R 2 = .34–.74), a measure of species abundance. CO 2 enrichment also increased soil moisture and decreased light levels within the canopy but did not affect soil inorganic nitrogen availability. Structural equation models fit across the soils suggested species‐specific controls on flowering in two general forms: (1) CO 2 effects on flowering culm count mediated by canopy light level and relative species AGB (species AGB/total AGB) or by soil moisture effects on flowering culm count; (2) effects of canopy light level or soil inorganic nitrogen on flowering and/or relative species AGB, but with no significant CO 2 effect. Understanding the heterogeneity in species responses to CO 2 enrichment in plant communities across soils in edaphically variable landscapes is critical to predict CO 2 effects on flowering and other plant fitness components, and species potential to adapt to future environmental changes.

Temporal heterogeneity increases with spatial heterogeneity in ecological communities - Scott L. Collins; Meghan L. Avolio; Corinna Gries; Lauren M. Hallett; Sally E. Koerner; Kimberly J. La Pierre; Andrew L. Rypel; Eric R. Sokol; Samuel B. Fey; Dan F. B. Flynn; Sydney K. Jones; Laura M. Ladwig; et al. (Ecology, 2018)
Heterogeneity is increasingly recognized as a foundational characteristic of ecological systems. Under global change, understanding temporal community heterogeneity is necessary for predicting the stability of ecosystem functions and services. Indeed, spatial heterogeneity is commonly used in alternative stable state theory as a predictor of temporal heterogeneity and therefore an early indicator of regime shifts. To evaluate whether spatial heterogeneity in species composition is predictive of temporal heterogeneity in ecological communities, we analyzed 68 community data sets spanning freshwater and terrestrial systems where measures of species abundance were replicated over space and time. Of the 68 data sets, 55 (81%) had a weak to strongly positive relationship between spatial and temporal heterogeneity, while in the remaining communities the relationship was weak to strongly negative (19%). Based on a mixed model analysis, we found a significant but weak overall positive relationship between spatial and temporal heterogeneity across all data sets combined, and within aquatic and terrestrial data sets separately. In addition, lifespan and successional stage were negatively and positively related to temporal heterogeneity, respectively. We conclude that spatial heterogeneity may be a predictor of temporal heterogeneity in ecological communities, and that this relationship may be a general property of many terrestrial and aquatic communities.

Cyclic and Fatigue Behaviour of Rock Materials: Review, Interpretation and Research Perspectives - B. Cerfontaine; F. Collin (Rock Mechanics and Rock Engineering, 2018)

The Effect of Vine Kill Method on Vine Kill, Tuber Skinning Injury, Tuber Yield and Size Distribution, and Tuber Nutrients and Phytonutrients in Two Potato Cultivars Grown for Early Potato Production - R. A. Boydston; D. A. Navarre; H. P. Collins; B. Chaves-Cordoba (American Journal of Potato Research, 2018)

Effect of repeated exposure to AQUI ‐S ® on the viability and growth of Neoparamoeba perurans - R J Chance; Z Allcock; C J Secombes; B Collet; C Collins (Journal of Fish Diseases, 2018)
There have been recent efforts amongst immunologists to develop approaches for following individual fish during challenges with viral and bacterial pathogens. This study contributes to assessing the feasibility of using such approaches to study amoebic gill disease ( AGD ). Neoparamoeba perurans , agent of AGD , has been responsible for widespread economic and fish loss in salmonid aquaculture. With the emergence of AGD in Europe, research into infection dynamics and host response has increased. This study investigated the effect of repeat exposure to anaesthesia, a necessary requirement when following disease progression in individual fish, on N. perurans . In vitro cultures of N. perurans were exposed every 4 days over a 28‐day period to AQUI ‐S ® (isoeugenol), a popular anaesthetic choice for AGD challenges, at a concentration and duration required to sedate post‐smolt salmonids. Population growth was measured by sequential counts of amoeba over the period, while viability of non‐attached amoeba in the culture was assessed with a vital stain. AQUI ‐S ® was found to be a suitable choice for in vivo ectoparasitic challenges with N. perurans during which repetitive anaesthesia is required for analysis of disease progression.

Comparison of tenofovir plasma and tissue exposure using a population pharmacokinetic model and bootstrap: a simulation study from observed data - Jon W. Collins; J. Heyward Hull; Julie B. Dumond (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Evaluation of Filtration and DNA Extraction Methods for Environmental DNA Biodiversity Assessments across Multiple Trophic Levels - Anni Djurhuus; Jesse Port; Collin J. Closek; Kevan M. Yamahara; Ofelia Romero-Maraccini; Kristine R. Walz; Dawn B. Goldsmith; Reiko Michisaki; Mya Breitbart; Alexandria B. Boehm; Francisco P. Chavez (Frontiers in Marine Science, 2017)

Validation of a New Elastoplastic Constitutive Model Dedicated to the Cyclic Behaviour of Brittle Rock Materials - B. Cerfontaine; R. Charlier; F. Collin; M. Taiebat (Rock Mechanics and Rock Engineering, 2017)

Inhibition of serotonin transporters disrupts the enhancement of fear memory extinction by 3,4-methylenedioxymethamphetamine (MDMA) - Matthew B. Young; Seth D. Norrholm; Lara M. Khoury; Tanja Jovanovic; Sheila A.M. Rauch; Collin M. Reiff; Boadie W. Dunlop; Barbara O. Rothbaum; Leonard L. Howell (Psychopharmacology, 2017)

Optimizing the Bioavailability of Subcutaneously Administered Biotherapeutics Through Mechanochemical Drivers - D. S. Collins; L. C. Kourtis; N. R. Thyagarajapuram; R. Sirkar; S. Kapur; M. W. Harrison; D. J. Bryan; G. B. Jones; J. M. Wright (Pharmaceutical Research, 2017)

Unique and isolated: population structure has implications for management of the endangered New Zealand sea lion - Catherine J. Collins; B. Louise Chilvers; Amy Osborne; Matt Taylor; Bruce C. Robertson (Conservation Genetics, 2017)

Time-matched analysis of DNA adduct formation and early gene expression as predictive tool for renal carcinogenesis in methylazoxymethanol acetate treated Eker rats - Valentina Klaus; Heinke Bastek; Katja Damme; Leonard B. Collins; Roland Frötschl; Norbert Benda; Dominik Lutter; Heidrun Ellinger-Ziegelbauer; James A. Swenberg; Daniel R. Dietrich; Kerstin Stemmer (Archives of Toxicology, 2017)

Tee L. Guidotti. Health and sustainability: An introduction - Mary B. Collins (Journal of Environmental Studies and Sciences, 2017)

Estimation of 3D Ground Reaction Force Using Nanocomposite Piezo-Responsive Foam Sensors During Walking - Parker G. Rosquist; Gavin Collins; A. Jake Merrell; Noelle J. Tuttle; James B. Tracy; Evan T. Bird; Matthew K. Seeley; David T. Fullwood; William F. Christensen; Anton E. Bowden (Annals of Biomedical Engineering, 2017)

Thermoregulation of the bovine scrotum 1: measurements of free-range animals in a paddock and pen - Andrea L. Wallage; S. D. Johnston; A. T. Lisle; L. Beard; A. M. Lees; C. W. Collins; J. B. Gaughan (International Journal of Biometeorology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

The Effect of Nitrogen Rate on Vine Kill, Tuber Skinning Injury, Tuber Yield and Size Distribution, and Tuber Nutrients and Phytonutrients in Two Potato Cultivars Grown for Early Potato Production - R. A. Boydston; D. A. Navarre; H. P. Collins; B. Chaves-Cordoba (American Journal of Potato Research, 2017)

Measurement of bovine body and scrotal temperature using implanted temperature sensitive radio transmitters, data loggers and infrared thermography - A. L. Wallage; J. B. Gaughan; A. T. Lisle; L. Beard; C. W. Collins; S. D. Johnston (International Journal of Biometeorology, 2017)

A kinematic investigation into the feeding behavior of the Goliath grouper Epinephelus itajara - A. B. Collins; P. J. Motta (Environmental Biology of Fishes, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Lizards fail to plastically adjust nesting behavior or thermal tolerance as needed to buffer populations from climate warming - Rory S. Telemeco; Brooke Fletcher; Ofir Levy; Angela Riley; Yesenia Rodriguez‐Sanchez; Colton Smith; Collin Teague; Amanda Waters; Michael J. Angilletta; Lauren B. Buckley (Global Change Biology, 2017)
Although observations suggest the potential for phenotypic plasticity to allow adaptive responses to climate change, few experiments have assessed that potential. Modeling suggests that Sceloporus tristichus lizards will need increased nest depth, shade cover, or embryonic thermal tolerance to avoid reproductive failure resulting from climate change. To test for such plasticity, we experimentally examined how maternal temperatures affect nesting behavior and embryonic thermal sensitivity. The temperature regime that females experienced while gravid did not affect nesting behavior, but warmer temperatures at the time of nesting reduced nest depth. Additionally, embryos from heat‐stressed mothers displayed increased sensitivity to high‐temperature exposure. Simulations suggest that critically low temperatures, rather than high temperatures, historically limit development of our study population. Thus, the plasticity needed to buffer this population has not been under selection. Plasticity will likely fail to compensate for ongoing climate change when such change results in novel stressors.

Multiple processes drive genetic structure of humpback whale ( Megaptera novaeangliae ) populations across spatial scales - Francine Kershaw; Inês Carvalho; Jacqueline Loo; Cristina Pomilla; Peter B. Best; Ken P. Findlay; Salvatore Cerchio; Tim Collins; Marcia H. Engel; Gianna Minton; Peter Ersts; Jaco Barendse; et al. (Molecular Ecology, 2017)
Elucidating patterns of population structure for species with complex life histories, and disentangling the processes driving such patterns, remains a significant analytical challenge. Humpback whale ( Megaptera novaeangliae ) populations display complex genetic structures that have not been fully resolved at all spatial scales. We generated a data set of nuclear markers for 3575 samples spanning the seven breeding stocks and substocks found in the South Atlantic and western and northern Indian Oceans. For the total sample, and males and females separately, we assessed genetic diversity, tested for genetic differentiation between putative populations and isolation by distance, estimated the number of genetic clusters without a priori population information and estimated rates of gene flow using maximum‐likelihood and Bayesian approaches. At the ocean basin scale, structure is governed by geographical distance ( IBD P F ST 0.034–0.161; P

Avian axons undergo Wallerian degeneration after injury and stress - John C. Bramley; Samantha V. A. Collins; Karen B. Clark; William J. Buchser (Journal of Comparative Physiology A, 2016)

Exhumation history of the Peake and Denison Inliers: insights from low-temperature thermochronology - J. W. Hall; S. Glorie; A. S. Collins; A. Reid; N. Evans; B. McInnes; J. Foden (Australian Journal of Earth Sciences, 2016)

Holocene reef evolution in a macrotidal setting: Buccaneer Archipelago, Kimberley Bioregion, Northwest Australia - Tubagus Solihuddin; Michael J. O’Leary; David Blakeway; Iain Parnum; Moataz Kordi; Lindsay B. Collins (Coral Reefs, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Preliminary evidence of reduced brain network activation in patients with post-traumatic migraine following concussion - Anthony P. Kontos; Amit Reches; R. J. Elbin; Dalia Dickman; Ilan Laufer; Amir B. Geva; Galit Shacham; Ryan DeWolf; Michael W. Collins (Brain Imaging and Behavior, 2016)

Incorporating Resource Protection Constraints in an Analysis of Landscape Fuel-Treatment Effectiveness in the Northern Sierra Nevada, CA, USA - Christopher B. Dow; Brandon M. Collins; Scott L. Stephens (Environmental Management, 2016)

Sediment‐phosphorus dynamics can shift aquatic ecology and cause downstream legacy effects after wildfire in large river systems - Monica B. Emelko; Micheal Stone; Uldis Silins; Don Allin; Adrian L. Collins; Chris H. S. Williams; Amanda M. Martens; Kevin D. Bladon (Global Change Biology, 2016)
Global increases in the occurrence of large, severe wildfires in forested watersheds threaten drinking water supplies and aquatic ecology. Wildfire effects on water quality, particularly nutrient levels and forms, can be significant. The longevity and downstream propagation of these effects as well as the geochemical mechanisms regulating them remain largely undocumented at larger river basin scales. Here, phosphorus (P) speciation and sorption behavior of suspended sediment were examined in two river basins impacted by a severe wildfire in southern Alberta, Canada. Fine‐grained suspended sediments ( TPP ) and particulate phosphorus forms (nonapatite inorganic P, apatite P, organic P), and the equilibrium phosphorus concentration ( EPC 0 ) of suspended sediment were assessed. Concentrations of TPP and the EPC 0 were significantly higher downstream of wildfire‐impacted areas compared to reference (unburned) upstream river reaches. Sediments from the burned tributary inputs contained higher levels of bioavailable particulate P ( NAIP ) – these effects were also observed downstream at larger river basin scales. The release of bioavailable P from postfire, P‐enriched fine sediment is a key mechanism causing these effects in gravel‐bed rivers at larger basin scales. Wildfire‐associated increases in NAIP and the EPC 0 persisted 6 and 7 years after wildfire. Accordingly, this work demonstrated that fine sediment in gravel‐bed rivers is a significant, long‐term source of in‐stream bioavailable P that contributes to a legacy of wildfire impacts on downstream water quality, aquatic ecology, and drinking water treatability.

Making literature reviews more reliable through application of lessons from systematic reviews - N.R. Haddaway; P. Woodcock; B. Macura; A. Collins (Conservation Biology, 2015)
Review articles can provide valuable summaries of the ever‐increasing volume of primary research in conservation biology. Where findings may influence important resource‐allocation decisions in policy or practice, there is a need for a high degree of reliability when reviewing evidence. However, traditional literature reviews are susceptible to a number of biases during the identification, selection, and synthesis of included studies (e.g., publication bias, selection bias, and vote counting). Systematic reviews, pioneered in medicine and translated into conservation in 2006, address these issues through a strict methodology that aims to maximize transparency, objectivity, and repeatability. Systematic reviews will always be the gold standard for reliable synthesis of evidence. However, traditional literature reviews remain popular and will continue to be valuable where systematic reviews are not feasible. Where traditional reviews are used, lessons can be taken from systematic reviews and applied to traditional reviews in order to increase their reliability. Certain key aspects of systematic review methods that can be used in a context‐specific manner in traditional reviews include focusing on mitigating bias; increasing transparency, consistency, and objectivity, and critically appraising the evidence and avoiding vote counting. In situations where conducting a full systematic review is not feasible, the proposed approach to reviewing evidence in a more systematic way can substantially improve the reliability of review findings, providing a time‐ and resource‐efficient means of maximizing the value of traditional reviews. These methods are aimed particularly at those conducting literature reviews where systematic review is not feasible, for example, for graduate students, single reviewers, or small organizations.

Challenges in transferring knowledge between scales in coastal sediment dynamics - Shari L. Gallop; Michael Collins; Charitha B. Pattiaratchi; Matthew J. Eliot; Cyprien Bosserelle; Marco Ghisalberti; Lindsay B. Collins; Ian Eliot; Paul L. A. Erftemeijer; Piers Larcombe; Ionan Marigómez; Tanya Stul; et al. (Frontiers in Marine Science, 2015)

Geochemistry of post-extinction microbialites as a powerful tool to assess the oxygenation of shallow marine water in the immediate aftermath of the end-Permian mass extinction - P. Y. Collin; S. Kershaw; N. Tribovillard; M. B. Forel; S. Crasquin (International Journal of Earth Sciences, 2015)

Rapid Colorimetric Detection of the Fungal Phytopathogen Synchytrium endobioticum Using Cyanine dye-Indicated PNA Hybridization - Janice Duy; Rosemary L. Smith; Scott D. Collins; Laurie B. Connell (American Journal of Potato Research, 2015)

Variations in reproductive potential between nearshore and offshore spawning contingents of hogfish in the eastern Gulf of Mexico - A. B. Collins; R. S. McBride (Fisheries Management and Ecology, 2015)
Hogfish, Lachnolaimus maximus (Walbaum), have multiple traits that confound measuring reproductive potential: they are protogynous, relatively long‐lived harem‐forming fish that spawn daily for months. Additionally, recent evidence demonstrates that size, age and timing of sex change vary on a spatial scale within the study area (West Florida shelf, USA ). This study investigates the effect of this spatial variation on hogfish reproductive potential by evaluating spawning seasonality, spawning frequency and batch fecundity using an indeterminate egg production model. Offshore females were larger than nearshore females, and batch fecundity was related in a log‐linear manner to female size. Gonad histology demonstrated a more protracted reproductive period for females offshore (8 months) than nearshore (4 months). Spatial variations in size coincide with ontogeny because hogfish move offshore with growth; however, even after accounting for fish size, offshore females spawned more. In areas where male removal rates are elevated, spawning harems are disrupted; thus, greater fishing effort nearshore may further reduce the reproductive potential of these females. These nearshore and offshore spawning components of the population are not genetically distinct, but instead represent two contingent spawning strategies that likely enhance total population stability and resilience of this stock in the eastern Gulf of Mexico.

Climate influences on water and sediment properties of Genovesa Crater Lake, Galápagos - Jessica L. Conroy; Diane M. Thompson; Aaron Collins; Jonathan T. Overpeck; Mark B. Bush; Julia E. Cole (Journal of Paleolimnology, 2014)

Invasive species contribute to biotic resistance: negative effect of caprellid amphipods on an invasive tunicate - Samuel B. Collin; Ladd E. Johnson (Biological Invasions, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

A comparison of the efficiency of ELISA and selected primer sets to detect Norovirus isolates in southern Ireland over a four-year period (2002-2006): variation in detection rates and evidence for continuing predominance of NoV GII.4 genotype - G. Lennon; N. Reidy; P. J. Collins; L. Gunn; P. V. Coyle; B. Cryan; S. Fanning; H. O’Shea (Archives of Virology, 2014)

Does temporal and spatial segregation explain the complex population structure of humpback whales on the coast of West Africa? - Inês Carvalho; Jacqueline Loo; Timothy Collins; Jaco Barendse; Cristina Pomilla; Matthew S. Leslie; Solange Ngouessono; Peter B. Best; Howard C. Rosenbaum (Marine Biology, 2014)

‘No thanks’—reasons why pregnant women declined an offer of cystic fibrosis carrier screening - L. Ioannou; J. Massie; S. Lewis; B. McClaren; V. Collins; M. B. Delatycki (Journal of Community Genetics, 2014)

Evaluation of Surfactant-Enhanced In Situ Chemical Oxidation (S-ISCO) in Contaminated Soil - Wei Hong Wang; George E. Hoag; John B. Collins; Ravi Naidu (Water, Air, & Soil Pollution, 2013)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

Probing the consequences of antenna modification in cyanobacteria - Michelle Liberton; Aaron M. Collins; Lawrence E. Page; William B. O’Dell; Hugh O’Neill; Volker S. Urban; Jerilyn A. Timlin; Himadri B. Pakrasi (Photosynthesis Research, 2013)

Isolation and characterization of 29 polymorphic microsatellite markers for the endangered Atlantic goliath grouper (Epinephelus itajara), and the Pacific goliath grouper (E. quinquefasciatus) - Seifu Seyoum; Michael D. Tringali; Brandon L. Barthel; Cecilia Puchulutegui; Michelle C. Davis; Angela B. Collins; Matthew T. Craig (Conservation Genetics Resources, 2013)

Probabilistic projections of transient climate change - Glen R. Harris; David M. H. Sexton; Ben B. B. Booth; Mat Collins; James M. Murphy (Climate Dynamics, 2013)

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

Faster scaling of visual neurons in cortical areas relative to subcortical structures in non-human primate brains - C. E. Collins; D. B. Leitch; P. Wong; J. H. Kaas; Suzana Herculano-Houzel (Brain Structure and Function, 2013)

The impact of the MJO on clusters of wintertime circulation anomalies over the North American region - Emily E. Riddle; Marshall B. Stoner; Nathaniel C. Johnson; Michelle L. L’Heureux; Dan C. Collins; Steven B. Feldstein (Climate Dynamics, 2013)

Hydrodynamic and sediment dynamic modifications of tidal flow in the near-field area of offshore breakwaters - Theocharis A. Plomaritis; Michael B. Collins (Ocean Dynamics, 2013)

Development and assessment of a biophysical dispersal model for sea lice - N K G Salama; C M Collins; J G Fraser; J Dunn; C C Pert; A G Murray; B Rabe (Journal of Fish Diseases, 2013)
Salmon aquaculture in Scotland continues to increase; however, one of the potential limitations to its further sustainable growth is the ectoparasitic sea louse L epeophtheirus salmonis . The industry in Scotland undertakes coordinated management procedures to control the levels of sea lice on farms in designated production areas. We developed a biophysical sea lice dispersal model for L och L innhe, one of the largest fjords on the west coast of Scotland, to provide further information to help establish more effective farm management areas. We successfully extend modelling principles previously applied to a small Scottish fjordic system. Modelling scenarios demonstrate heterogeneity in the distribution of sea lice within the system and simulations, suggesting that lice could be transmitted up to 30 km. The scenarios are assessed by comparing model predictions against lice sampled by both planktonic trawls and settlement on sentinel caged fish. The model predicts the ranked abundance of both planktonic and settled lice assuming that the lice input to the system is relative to host biomass. Data collection is ongoing for undertaking and assessing additional scenarios.

Footprints of selection in wild populations of B icyclus anynana along a latitudinal cline - M. A. de Jong; S. Collins; P. Beldade; P. M. Brakefield; B. J. Zwaan (Molecular Ecology, 2013)
One of the major questions in ecology and evolutionary biology is how variation in the genome enables species to adapt to divergent environments. Here, we study footprints of thermal selection in candidate genes in six wild populations of the afrotropical butterfly Bicyclus anynana sampled along a c . 3000 km latitudinal cline. We sequenced coding regions of 31 selected genes with known functions in metabolism, pigment production, development and heat shock responses. These include genes for which we expect a priori a role in thermal adaptation and, thus, varying selection pressures along a latitudinal cline, and genes we do not expect to vary clinally and can be used as controls. We identified amino acid substitution polymorphisms in 13 genes and tested these for clinal variation by correlation analysis of allele frequencies with latitude. In addition, we used two F ST ‐based outlier methods to identify loci with higher population differentiation than expected under neutral evolution, while accounting for potentially confounding effects of population structure and demographic history. Two metabolic enzymes of the glycolytic pathway, UGP and Treh, showed clinal variation. The same loci showed elevated population differentiation and were identified as significant outliers. We found no evidence of clines in the pigmentation genes, heat shock proteins and developmental genes. However, we identified outlier loci in more localized parts of the range in the pigmentation genes yellow and black . We discuss that the observed clinal variation and elevated population divergence in UGP and Treh may reflect adaptation to a geographic thermal gradient.

Above- and belowground responses to nitrogen addition in a Chihuahuan Desert grassland - Laura M. Ladwig; Scott L. Collins; Amaris L. Swann; Yang Xia; Michael F. Allen; Edith B. Allen (Oecologia, 2012)

Transgenic Stra8-EYFP pigs: a model for developing male germ cell technologies - Jeffrey R. Sommer; Lauren R. Jackson; Sean G. Simpson; Edwin B. Collins; Jorge A. Piedrahita; Robert M. Petters (Transgenic Research, 2012)

Woody encroachment decreases diversity across North American grasslands and savannas - Zakary Ratajczak; Jesse B. Nippert; Scott L. Collins (Ecology, 2012)
Woody encroachment is a widespread and acute phenomenon affecting grasslands and savannas worldwide. We performed a meta‐analysis of 29 studies from 13 different grassland/savanna communities in North America to determine the consequences of woody encroachment on plant species richness. In all 13 communities, species richness declined with woody plant encroachment (average decline = 45%). Species richness declined more in communities with higher precipitation ( r 2 = 0.81) and where encroachment was associated with a greater change in annual net primary productivity (ANPP; r 2 = 0.69). Based on the strong positive correlation between precipitation and ANPP following encroachment ( r 2 = 0.87), we hypothesize that these relationships occur because water‐limited woody plants experience a greater physiological and demographic release as precipitation increases. The observed relationship between species richness and ANPP provides support for the theoretical expectation that a trade‐off occurs between richness and productivity in herbaceous communities. We conclude that woody plant encroachment leads to significant declines in species richness in North American grassland/savanna communities.

Novel Alu retrotransposon insertion leading to Alström syndrome - Mustafa Taşkesen; Gayle B. Collin; Alexei V. Evsikov; Ayşegül Güzel; R. Köksal Özgül; Jan D. Marshall; Jürgen K. Naggert (Human Genetics, 2012)

Mutant and Overexpression Analysis of a C2H2 Single Zinc Finger Gene of Arabidopsis - Randy D. Dinkins; Venkata S. Tavva; S. Reddy Palli; Glenn B. Collins (Plant Molecular Biology Reporter, 2012)

Functional haplotypes of Fc gamma (Fcγ) receptor (FcγRIIA and FcγRIIIB) predict risk to repeated episodes of severe malarial anemia and mortality in Kenyan children - Collins Ouma; Gregory C. Davenport; Steven Garcia; Prakasha Kempaiah; Ateefa Chaudhary; Tom Were; Samuel B. Anyona; Evans Raballah; Stephen N. Konah; James B. Hittner; John M. Vulule; John M. Ong’echa; et al. (Human Genetics, 2012)

Phylogeography and bindin evolution in Arbacia , a sea urchin genus with an unusual distribution - H. A. LESSIOS; S. LOCKHART; R. COLLIN; G. SOTIL; P. SANCHEZ‐JEREZ; K. S. ZIGLER; A. F. PEREZ; M. J. GARRIDO; L. B. GEYER; G. BERNARDI; V. D. VACQUIER; R. HAROUN; et al. (Molecular Ecology, 2012)
Among shallow water sea urchin genera, Arbacia is the only genus that contains species found in both high and low latitudes. In order to determine the geographical origin of the genus and its history of speciation events, we constructed phylogenies based on cytochrome oxidase I and sperm bindin from all its species. Both the mitochondrial and the nuclear gene genealogies show that Arbacia originated in the temperate zone of the Southern Hemisphere and gave rise to three species in the eastern Pacific, which were then isolated from the Atlantic by the Isthmus of Panama. The mid‐Atlantic barrier separated two additional species. The bindin data suggest that selection against hybridization is not important in the evolution of this molecule in this genus. Metz et al. in a previous publication found no evidence of selection on bindin of Arbacia and suggested that this might be due to allopatry between species, which obviated the need for species recognition. This suggestion formed the basis of the conclusion, widely spread in the literature, that the source of selection on sea urchin bindin (where it does occur) was reinforcement. However, the range of Arbacia spatuligera overlaps with that of two other species of Arbacia , and our data show that it is hybridizing with one of them. We found that even in the species that overlap geographically, there are no deviations from selective neutrality in the evolution of bindin.

Genotoxicity in Atlantic killifish (Fundulus heteroclitus) from a PAH-contaminated Superfund site on the Elizabeth River, Virginia - Dawoon Jung; Cole W. Matson; Leonard B. Collins; Geoff Laban; Heather M. Stapleton; John W. Bickham; James A. Swenberg; Richard T. Di Giulio (Ecotoxicology, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Fine mapping the KLK3 locus on chromosome 19q13.33 associated with prostate cancer susceptibility and PSA levels - Hemang Parikh; Zhaoming Wang; Kerry A. Pettigrew; Jinping Jia; Sarah Daugherty; Meredith Yeager; Kevin B. Jacobs; Amy Hutchinson; Laura Burdett; Michael Cullen; Liqun Qi; Joseph Boland; et al. (Human Genetics, 2011)

Climate model errors, feedbacks and forcings: a comparison of perturbed physics and multi-model ensembles - Matthew Collins; Ben B. B. Booth; B. Bhaskaran; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2011)

Simulating Fire and Forest Dynamics for a Landscape Fuel Treatment Project in the Sierra Nevada - Brandon M. Collins; Scott L. Stephens; Gary B. Roller; John J. Battles (Forest Science, 2011)
We evaluated an actual landscape fuel treatment project that was designed by local US Forest Service managers in the northern Sierra Nevada. We modeled the effects of this project on reducing landscape-level fire behavior at multiple time steps, up to nearly 30 years beyond treatment implementation. In addition, we modeled planned treatments under multiple diameter-limited thinning scenarios to assess potential impacts on fuel treatment effectiveness. The planned fuel treatments reduced modeled conditional burn probabilities substantially across the landscape relative to those for a scenario with no simulated treatments. This reduction relative to that for the no treatment landscape was evident approximately 20 years after simulated treatment implementation. Although diameter-limited thinning scenarios resulted in different residual forest stand structures, we detected no real differences in modeled landscape-level burn probabilities. The modeling adaptations we made with respect to fuel model selection and simulated ingrowth/regeneration over simulated time, as well as incorporation of variable winds in fire simulations, collectively contribute to a robust analysis of the study area.

The Effect of a Cationic Porphyrin on Pseudomonas aeruginosa Biofilms - Tracy L. Collins; Elizabeth A. Markus; Daniel J. Hassett; Jayne B. Robinson (Current Microbiology, 2010)

Prey life‐history and bioenergetic responses across a predation gradient - M. D. Rennie; C. F. Purchase; B. J. Shuter; N. C. Collins; P. A. Abrams; G. E. Morgan (Journal of Fish Biology, 2010)
To evaluate the importance of non‐consumptive effects of predators on prey life histories under natural conditions, an index of predator abundance was developed for naturally occurring populations of a common prey fish, the yellow perch Perca flavescens , and compared to life‐history variables and rates of prey energy acquisition and allocation as estimated from mass balance models. The predation index was positively related to maximum size and size at maturity in both male and female P. flavescens , but not with life span or reproductive investment. The predation index was positively related to size‐adjusted specific growth rates and growth efficiencies but negatively related to model estimates of size‐adjusted specific consumption and activity rates in both vulnerable (small) and invulnerable (large) size classes of P. flavescens . These observations suggest a trade‐off between growth and activity rates, mediated by reduced activity in response to increasing predator densities. Lower growth rates and growth efficiencies in populations with fewer predators, despite increased consumption suggests either 1) a reduction in prey resources at lower predator densities or 2) an intrinsic cost of rapid prey growth that makes it unfavourable unless offset by a perceived threat of predation. This study provides evidence of trade‐offs between growth and activity rates induced by predation risk in natural prey fish populations and illustrates how behavioural modification induced through predation can shape the life histories of prey fish species.

Petrographical and geochemical evidences for paragenetic sequence interpretation of diagenesis in mixed siliciclastic–carbonate sediments: Mozduran Formation (Upper Jurassic), south of Agh-Darband, NE Iran - A. Mahboubi; R. Moussavi-Harami; S. J. Carpenter; A. Aghaei; L. B. Collins (Carbonates and Evaporites, 2010)

Legal Liability as Poison Center Consultant - Steven E. Aks; Collin B. Williams; Sean M. Bryant (Journal of Medical Toxicology, 2010)

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis - G. B. Rogers; L. E. Russell; P. G. Preston; P. Marsh; J. E. Collins; J. Saunders; J. Sutton; D. Fine; K. D. Bruce; M. Wright (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The role of atmosphere and ocean physical processes in ENSO in a perturbed physics coupled climate model - S. Y. Philip; M. Collins; G. J. van Oldenborgh; B. J. J. M. van den Hurk (Ocean Science, 2010)
We examine the behaviour of the El Niño – Southern Oscillation (ENSO) in an ensemble of global climate model simulations with perturbations to parameters in the atmosphere and ocean components respectively. The influence of the uncertainty in these parametrisations on ENSO are investigated systematically. The ensemble exhibits a range of different ENSO behaviour in terms of the amplitude and spatial structure of the sea surface temperature (SST) variability. The nature of the individual feedbacks that operate within the ENSO system are diagnosed using an Intermediate Complexity Model (ICM), which has been used previously to examine the diverse ENSO behaviour of the CMIP3 multi-model ensemble. Unlike in that case, the ENSO in these perturbed physics experiments is not principally controlled by variations in the mean climate state. Rather the parameter perturbations influence the ENSO characteristics by modifying the coupling feedbacks within the cycle. The associated feedbacks that contribute most to the ensemble variations are the response of SST to local wind variability and damping, followed by the response of SST to thermocline anomalies and the response of the zonal wind stress to those SST anomalies. Atmospheric noise amplitudes and oceanic processes play a relatively minor role.

The role of geomorphology in evaluating remediation options for floodplain wetlands: the case of Ramsar-listed Seekoeivlei, eastern South Africa - T. S. McCarthy; S. Tooth; D. C. Kotze; N. B. Collins; G. Wandrag; T. Pike (Wetlands Ecology and Management, 2010)

Trusting Emergence: Some Experiences of Learning about Integrated Catchment Science with the Environment Agency of England and Wales - Kevin B. Collins; Ray L. Ison (Water Resources Management, 2010)

A comprehensive resequence analysis of the KLK15–KLK3–KLK2 locus on chromosome 19q13.33 - Hemang Parikh; Zuoming Deng; Meredith Yeager; Joseph Boland; Casey Matthews; Jinping Jia; Irene Collins; Ariel White; Laura Burdett; Amy Hutchinson; Liqun Qi; Jennifer A. Bacior; et al. (Human Genetics, 2010)

Anti-NMDA receptor encephalitis: report of ten cases and comparison with viral encephalitis - M. S. Gable; S. Gavali; A. Radner; D. H. Tilley; B. Lee; L. Dyner; A. Collins; A. Dengel; J. Dalmau; C. A. Glaser (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Ostracods (Crustacea) and water oxygenation in the earliest Triassic of South China: implications for oceanic events at the end-Permian mass extinction - M-B. Forel; S. Crasquin; S. Kershaw; Q. L. Feng; P-Y. Collin (Australian Journal of Earth Sciences, 2009)

Microbialites as disaster forms in anachronistic facies following the end-Permian mass extinction: a discussion - S. Kershaw; S. Crasquin; P-Y. Collin; Y. Li; Q. Feng; M-B. Forel (Australian Journal of Earth Sciences, 2009)

Physical analysis of the complex rye (Secale cereale L.) Alt4 aluminium (aluminum) tolerance locus using a whole-genome BAC library of rye cv. Blanco - B.-J. Shi; J. P. Gustafson; J. Button; J. Miyazaki; M. Pallotta; N. Gustafson; H. Zhou; P. Langridge; N. C. Collins (Theoretical and Applied Genetics, 2009)

Varietal and chromosome 2H locus-specific frost tolerance in reproductive tissues of barley (Hordeum vulgare L.) detected using a frost simulation chamber - Andrew Chen; Lawrence V. Gusta; Anita Brûlé-Babel; Richard Leach; Ute Baumann; Geoffrey B. Fincher; Nicholas C. Collins (Theoretical and Applied Genetics, 2009)

Genes and traits associated with chromosome 2H and 5H regions controlling sensitivity of reproductive tissues to frost in barley - Andrew Chen; Jason Reinheimer; Anita Brûlé-Babel; Ute Baumann; Margaret Pallotta; Geoffrey B. Fincher; Nicholas C. Collins (Theoretical and Applied Genetics, 2009)

Flt-2L, a locus in barley controlling flowering time, spike density, and plant height - Andrew Chen; Ute Baumann; Geoffrey B. Fincher; Nicholas C. Collins (Functional & Integrative Genomics, 2009)

Summer dietary nitrogen availability as a potential bottom‐up constraint on moose in south‐central Alaska - Scott H. McArt; Donald E. Spalinger; William B. Collins; Erik R. Schoen; Timothy Stevenson; Michele Bucho (Ecology, 2009)
Recent studies suggest that the growth and fecundity of northern ungulates may be coupled to their summer nutrition. Here, we compare summer dietary nitrogen availability of the five major browse plants (comprising ∼79% of the diet) of moose ( Alces alces ) in Denali National Park and Nelchina Basin, Alaska, USA. In recent years the productivity of Denali moose has been significantly higher than that of Nelchina moose, prompting this comparison. We examined the phenological progression of leaf nitrogen concentration, tannin–protein precipitation capacity, and digestible protein over three summers in both regions. We then modeled the potential nutritional consequences for a cow moose consuming representative diets on each range, predicting both net protein intake (NPI) and lean body mass accumulation each year. We found that leaf nitrogen and digestible protein decreased, while tannin–protein precipitation capacity increased throughout the summer for all forages. There was 23% more digestible protein in Denali leaves than Nelchina leaves on average, and this difference was significant in all three years. Tannins accounted for a large (mean = 46%) reduction in protein availability, suggesting a key role of these secondary compounds in the nitrogen balance of moose in these regions. Finally, our NPI model predicted that Denali cows were in positive protein balance 17 days longer than Nelchina cows and accumulated 18 kg more lean body mass over the summer, on average. We conclude that summer dietary nitrogen availability may act as a nutritional constraint on moose and suggest that more emphasis be placed on elucidating its role in population dynamics and conservation of northern ungulates.

Estimating landscape‐scale vegetation carbon stocks using airborne multi‐frequency polarimetric synthetic aperture radar (SAR) in the savannahs of north Australia - J. N. Collins; L. B. Hutley; R. J. Williams; G. Boggs; D. Bell; R. Bartolo (International Journal of Remote Sensing, 2009)

Haplotypes of IL-10 promoter variants are associated with susceptibility to severe malarial anemia and functional changes in IL-10 production - Collins Ouma; Gregory C. Davenport; Tom Were; Michael F. Otieno; James B. Hittner; John M. Vulule; Jeremy Martinson; John M. Ong’echa; Robert E. Ferrell; Douglas J. Perkins (Human Genetics, 2008)

Spatial Distribution and Long-term Movement Patterns of Cownose Rays Rhinoptera bonasus Within an Estuarine River - Angela B. Collins; Michelle R. Heupel; Colin A. Simpfendorfer (Estuaries and Coasts, 2008)

RANK CLOCKS AND PLANT COMMUNITY DYNAMICS - Scott L. Collins; Katharine N. Suding; Elsa E. Cleland; Michael Batty; Steven C. Pennings; Katherine L. Gross; James B. Grace; Laura Gough; Joe E. Fargione; Christopher M. Clark (Ecology, 2008)
Summarizing complex temporal dynamics in communities is difficult to achieve in a way that yields an intuitive picture of change. Rank clocks and rank abundance statistics provide a graphical and analytical framework for displaying and quantifying community dynamics. We used rank clocks, in which the rank order abundance for each species is plotted over time in temporal clockwise direction, to display temporal changes in species abundances and richness. We used mean rank shift and proportional species persistence to quantify changes in community structure in long‐term data sets from fertilized and control plots in a late successional old field, frequently and infrequently burned tallgrass prairie, and Chihuahuan desert grassland and shrubland communities. Rank clocks showed that relatively constant species richness masks considerable temporal dynamics in relative species abundances. In the old field, fertilized plots initially experienced high mean rank shifts that stabilized rapidly below that of unfertilized plots. Rank shifts were higher in infrequently burned vs. annually burned tallgrass prairie and in desert grassland compared to shrubland vegetation. Proportional persistence showed that arid grasslands were more dynamic than mesic grasslands. We conclude that rank clocks and rank abundance statistics provide important insights into community dynamics that are often hidden by traditional univariate approaches.

Automated Kerogen Classification in Microscope Images of Dispersed Kerogen Preparation - L. I. Kuncheva; J. J. Charles; N. Miles; A. Collins; B. Wells; I. S. Lim (Mathematical Geosciences, 2008)

Single cell adhesion measuring apparatus (SCAMA): application to cancer cell lines of different metastatic potential and voltage-gated Na+ channel expression - Christopher P. Palmer; Maria E. Mycielska; Hakan Burcu; Kareem Osman; Timothy Collins; Rachel Beckerman; Rebecca Perrett; Helen Johnson; Ebru Aydar; Mustafa B. A. Djamgoz (European Biophysics Journal, 2008)

Shrub encroachment in North American grasslands: shifts in growth form dominance rapidly alters control of ecosystem carbon inputs - ALAN K. KNAPP; JOHN M. BRIGGS; SCOTT L. COLLINS; STEVEN R. ARCHER; M. SYNDONIA BRET‐HARTE; BRENT E. EWERS; DEBRA P. PETERS; DONALD R. YOUNG; GAIUS R. SHAVER; ELISE PENDALL; MEAGAN B. CLEARY (Global Change Biology, 2008)
Shrub encroachment into grass‐dominated biomes is occurring globally due to a variety of anthropogenic activities, but the consequences for carbon (C) inputs, storage and cycling remain unclear. We studied eight North American graminoid‐dominated ecosystems invaded by shrubs, from arctic tundra to Atlantic coastal dunes, to quantify patterns and controls of C inputs via aboveground net primary production (ANPP). Across a fourfold range in mean annual precipitation (MAP), a key regulator of ecosystem C input at the continental scale, shrub invasion decreased ANPP in xeric sites, but dramatically increased ANPP (>1000 g m −2 ) at high MAP, where shrub patches maintained extraordinarily high leaf area. Concurrently, the relationship between MAP and ANPP shifted from being nonlinear in grasslands to linear in shrublands. Thus, relatively abrupt (

Determination of Iodine in Low Mass Human Hair Samples by Inductively Coupled Plasma Mass Spectrometry - K. E. Levine; A. S. Essader; F. X. Weber; J. M. Perlmutter; L. S. Milstein; R. A. Fernando; M. A. Levine; B. J. Collins; J. B. Adams; P. M. Grohse (Bulletin of Environmental Contamination and Toxicology, 2007)

PilJ Localizes to Cell Poles and Is Required for Type IV Pilus Extension in Pseudomonas aeruginosa - Paul A. DeLange; Tracy L. Collins; George E. Pierce; Jayne B. Robinson (Current Microbiology, 2007)

Development of a tightly regulated and highly inducible ecdysone receptor gene switch for plants through the use of retinoid X receptor chimeras - Venkata S. Tavva; Randy D. Dinkins; Subba R. Palli; Glenn B. Collins (Transgenic Research, 2007)

Residence and movement patterns of cownose rays Rhinoptera bonasus within a south‐west Florida estuary - A. B. Collins; M. R. Heupel; P. J. Motta (Journal of Fish Biology, 2007)
Between July 2003 and November 2004, 21 cownose rays Rhinoptera bonasus were tagged and tracked within Pine Island Sound estuary, Florida, using passive acoustic telemetry. Residence time of individuals ranged between 1 and 102 days. No relationship was detected between ray activity and tidal stage or time of day. Minimum convex polygons (MCP) and kernel utilization distributions (KUD) were calculated over several time frames to demonstrate the extent of an animal’s home range and core areas of use. Total MCPs ranged between 0·81 and 71·78 km 2 (mean = 22·01 km 2 ), with daily MCPs as large as 25·8 km 2 . Total 95% KUDs ranged between 0·18 and 62·44 km 2 (mean = 22·63 km 2 ), while total 50% KUDs were smaller, ranging from 0·09 to 9·68 km 2 (mean = 3·33 km 2 ). Both MCP and KUD areas exhibited a positive relationship with residence time and R. bonasus size. As mobile, pelagic swimmers capable of traversing large distances, these data show that cownose rays travel extensively throughout this estuary, yet may remain within very small areas for extended periods.

Captive breeding and embryonic development of Chiloscyllium punctatum Muller & Henle, 1838 (Elasmobranchii: Hemiscyllidae) - B. K. Harahush; A. B. P. Fischer; S. P. Collin (Journal of Fish Biology, 2007)
The fecundity, embryonic development, growth and viability of captive Chiloscyllium punctatum were investigated over two breeding and laying seasons. Chiloscyllium punctatum is an oviparous species, which lays rectangular eggs from late July to February. The six adult female C. punctatum in the open ocean display tank at UnderWater World, Mooloolaba, Australia laid a total of 692 eggs between July 2004 and February 2006, with 228 of those being viable. This equates to each female laying 115·3 eggs over the two seasons, with 38 viable. The embryos are first visible to the naked eye at c . 18 days post deposition (dpd), while pre‐hatching is first seen c . 35 dpd, and the embryos hatch at an average of 153 dpd (temperature 21–25° C). Embryonic growth is most rapid from 99 dpd until hatching. An average of 21·4% of the eggs hatched over the two seasons.

A derivation of roughness correlation length for parameterizing radar backscatter models - M. M. Rahman; M. S. Moran; D. P. Thoma; R. Bryant; E. E. Sano; C. D. Holifield Collins; S. Skirvin; C. Kershner; B. J. Orr (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Environmental and plant community determinants of species loss following nitrogen enrichment - Chris M. Clark; Elsa E. Cleland; Scott L. Collins; Joseph E. Fargione; Laura Gough; Katherine L. Gross; Steven C. Pennings; Katherine N. Suding; James B. Grace (Ecology Letters, 2007)
Global energy use and food production have increased nitrogen inputs to ecosystems worldwide, impacting plant community diversity, composition, and function. Previous studies show considerable variation across terrestrial herbaceous ecosystems in the magnitude of species loss following nitrogen (N) enrichment. What controls this variation remains unknown. We present results from 23 N‐addition experiments across North America, representing a range of climatic, soil and plant community properties, to determine conditions that lead to greater diversity decline. Species loss in these communities ranged from 0 to 65% of control richness. Using hierarchical structural equation modelling, we found greater species loss in communities with a lower soil cation exchange capacity, colder regional temperature, and larger production increase following N addition, independent of initial species richness, plant productivity, and the relative abundance of most plant functional groups. Our results indicate sensitivity to N addition is co‐determined by environmental conditions and production responsiveness, which overwhelm the effects of initial community structure and composition.

Increased α-tocopherol content in soybean seed overexpressing the Perilla frutescens γ-tocopherol methyltransferase gene - Venkata S. Tavva; Yul-Ho Kim; Isabelle A. Kagan; Randy D. Dinkins; Kyung-Hwan Kim; Glenn B. Collins (Plant Cell Reports, 2006)

Frequency distributions of transient regional climate change from perturbed physics ensembles of general circulation model simulations - G. R. Harris; D. M. H. Sexton; B. B. B. Booth; M. Collins; J. M. Murphy; M. J. Webb (Climate Dynamics, 2006)

North Atlantic Oscillation response to transient greenhouse gas forcing and the impact on European winter climate: a CMIP2 multi-model assessment - D. B. Stephenson; V. Pavan; M. Collins; M. M. Junge; R. Quadrelli (Climate Dynamics, 2006)

Towards quantifying uncertainty in transient climate change - Matthew Collins; Ben B. B. Booth; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2006)

A Modified Method for Determining Tannin–Protein Precipitation Capacity Using Accelerated Solvent Extraction (ASE) and Microplate Gel Filtration - Scott H. McArt; Donald E. Spalinger; John M. Kennish; William B. Collins (Journal of Chemical Ecology, 2006)

Residency and movement patterns of bonnethead sharks, Sphyrna tiburo, in a large Florida estuary - Michelle R. Heupel; Colin A. Simpfendorfer; Angela B. Collins; John P. Tyminski (Environmental Biology of Fishes, 2006)

Targeted overexpression of the Escherichia coli MinC protein in higher plants results in abnormal chloroplasts - Venkata S. Tavva; Glenn B. Collins; Randy D. Dinkins (Plant Cell Reports, 2006)

Soil microbial, fungal, and nematode responses to soil fumigation and cover crops under potato production - H. P. Collins; A. Alva; R. A. Boydston; R. L. Cochran; P. B. Hamm; A. McGuire; E. Riga (Biology and Fertility of Soils, 2006)

Reconsidering the human immunoglobulin heavy-chain locus: - C. E. H. Lee; B. Gaëta; H. R. Malming; M. E. Bain; W. A. Sewell; A. M. Collins (Immunogenetics, 2006)

Completion of the Sequence of a Cetacean Morbillivirus and Comparative Analysis of the Complete Genome Sequences of Four Morbilliviruses - B. K. Rima; A. M. J. Collin; J. A. P. Earle (Virus Genes, 2005)

Evidence for emergence of an amphibian iridoviral disease because of human‐enhanced spread - J. K. JANCOVICH; E. W. DAVIDSON; N. PARAMESWARAN; J. MAO; V. G. CHINCHAR; J. P. COLLINS; B. L. JACOBS; A. STORFER (Molecular Ecology, 2005)
Our understanding of origins and spread of emerging infectious diseases has increased dramatically because of recent applications of phylogenetic theory. Iridoviruses are emerging pathogens that cause global amphibian epizootics, including tiger salamander ( Ambystoma tigrinum ) die‐offs throughout western North America. To explain phylogeographical relationships and potential causes for emergence of western North American salamander iridovirus strains, we sequenced major capsid protein and DNA methyltransferase genes, as well as two noncoding regions from 18 geographically widespread isolates. Phylogenetic analyses of sequence data from the capsid protein gene showed shallow genetic divergence ( Ranavirus , suggesting a single introduction and radiation. Analysis of capsid protein sequences also provided support for a closer relationship of tiger salamander virus strains to those isolated from sport fish (e.g. rainbow trout) than other amphibian isolates. Despite monophyly based on capsid protein sequences, there was low genetic divergence among all strains ( Ambystoma mexicanum ) colony. Human enhancement of viral movement is a mechanism consistent with these results. These findings suggest North American salamander ranaviruses cause emerging disease, as evidenced by apparent recent spread over a broad geographical area.

Analysis of the Agrobacterium tumefaciens pTiChry5 6b Promoter - M. S. Srinivasa Reddy; Santanu Dasgupta; Linda Rymarquis; Glenn B. Collins; Randy Dinkins (Journal of Plant Biochemistry and Biotechnology, 2003)

Gene silencing in transgenic soybean plants transformed via particle bombardment - M. S. Srinivasa Reddy; Randy D. Dinkins; Glenn B. Collins (Plant Cell Reports, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Sequence Analysis of the Washington/1964 strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild Type Recombinant HPIV1 Produced by Reverse Genetics - J. T. Newman; S. R. Surman; J. M. Riggs; Chris T. Hansen; P. L. Collins; B. R. Murphy; M.H. Skiadopoulos (Virus Genes, 2003)

Parabolic Equation Techniques for Seismic Waves - W. Jerzak; M. D. Collins; R. B. Evans; J. F. Lingevitch; W. L. Siegmann (Pure and Applied Geophysics, 2002)

Overexpression of the Arabidopsis thaliana MinD1 gene alters chloroplast size and number in transgenic tobacco plants - Randy Dinkins; Srinivasa M. Reddy; Mei Leng; Glenn B. Collins (Planta, 2001)

A quantitative nature of somatic embryogenesis in soybean - Antonio O. Di Mauro; Roberto C. De Oliveira; Gisele A. Bonacin; João A. De Oliveira; Sonia M. Z. Di Mauro; Glenn B. Collins (In Vitro Cellular & Developmental Biology - Plant, 2001)

Increased sulfur amino acids in soybean plants overexpressing the maize 15 kDa zein protein - Randy D. Dinkins; M. S. Srinivasa Reddy; Curtis A. Meurer; Bo Yan; Harold Trick; Françoise Thibaud-Nissen; John J. Finer; Wayne A. Parrott; Glenn B. Collins (In Vitro Cellular & Developmental Biology - Plant, 2001)

Hydrology effects on propagule bank expression and vegetation in six Carolina bays - B. S. Collins; L. L. Battaglia (Community Ecology, 2001)

Trends in extreme daily rainfall and temperature in Southeast Asia and the South Pacific: 1961–1998 - M.J. Manton; P.M. Della‐Marta; M.R. Haylock; K.J. Hennessy; N. Nicholls; L.E. Chambers; D.A. Collins; G. Daw; A. Finet; D. Gunawan; K. Inape; H. Isobe; et al. (International Journal of Climatology, 2001)
Trends in extreme daily temperature and rainfall have been analysed from 1961 to 1998 for Southeast Asia and the South Pacific. This 38‐year period was chosen to optimize data availability across the region. Using high‐quality data from 91 stations in 15 countries, significant increases were detected in the annual number of hot days and warm nights, with significant decreases in the annual number of cool days and cold nights. These trends in extreme temperatures showed considerable consistency across the region. Extreme rainfall trends were generally less spatially coherent than were those for extreme temperature. The number of rain days (with at least 2 mm of rain) has decreased significantly throughout Southeast Asia and the western and central South Pacific, but increased in the north of French Polynesia, in Fiji, and at some stations in Australia. The proportion of annual rainfall from extreme events has increased at a majority of stations. The frequency of extreme rainfall events has declined at most stations (but not significantly), although significant increases were detected in French Polynesia. Trends in the average intensity of the wettest rainfall events each year were generally weak and not significant. Copyright © 2001 Royal Meteorological Society

An Assessment of HOx Chemistry in the Tropical Pacific Boundary Layer: Comparison of Model Simulations with Observations Recorded during PEM Tropics A - G. Chen; D. Davis; J. Crawford; B. Heikes; D. O'Sullivan; M. Lee; F. Eisele; L. Mauldin; D. Tanner; J. Collins; J. Barrick; B. Anderson; et al. (Journal of Atmospheric Chemistry, 2001)

Application methodology of ca and/or fumigation including use of carbon dioxide under increased pressure - C. J. Waterford; P. P. Asher; M. G. Andrada; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; P. V. Herrera; M. G. Andrada; Ma. Elvira M. Martinez; R. P. Estigoy; P. Williams; R. Ryan; R. Cavasin; et al. (Phytoparasitica, 2001)

The internal climate variability of HadCM3, a version of the Hadley Centre coupled model without flux adjustments - M. Collins; S. F. B. Tett; C. Cooper (Climate Dynamics, 2001)

Embryogenic response of multiple soybean [Glycine max (L.) merr.] cultivars across three locations - C. A. Meurer; R. D. Dinkins; C. T. Redmond; K. P. McAllister; D. T. Tucker; D. R. Walker; W. A. Parrott; H. N. Trick; J. S. Essig; H. M. Frantz; J. J. Finer; G. B. Collins (In Vitro Cellular & Developmental Biology - Plant, 2001)

Agrobacterium tumefaciens - mediated transformation of soybean [ Glycine max (L.) Merrill.] using immature zygotic cotyledon explants - B. Yan; M. S. Srinivasa Reddy; G. B. Collins; R. D. Dinkins (Plant Cell Reports, 2000)

Genetic variation within and among patches of the clonal species, Vaccinium stamineum L. - S. A. Kreher; S. A. Foré; B. S. Collins (Molecular Ecology, 2000)
Once thought to be dominated by a few genets, clonal plant populations can contain high levels of genetic diversity. Sexual reproduction and vegetative growth strategy affect the amount and distribution of genetic diversity within clonal plant populations. We determined the scale of genetic diversity in a population of Vaccinium stamineum , a clonal shrub that forms discrete patches. Using the random amplified polymorphic DNA (RAPD) technique, we surveyed the genetic diversity of V. stamineum within and among patches from a 1‐ha site. We found 67 unique RAPD profiles among the 99 sampled individuals from 22 patches. In two patches, all the sampled individuals had the same RAPD profile. In seven patches, every individual sampled had a different RAPD profile. The remaining patches showed mixed RAPD profiles which suggested both clonal and sexual reproduction. Each unique RAPD profile was restricted to one patch (with one exception), which suggests that clonal growth occurs at the patch scale. High levels of genetic variation within some patches may be explained by somatic mutation; however, seedling recruitment is a more likely explanation.

Annual cycle of energy allocation to growth and reproduction of yellow perch - B. A. Henderson; T. Trivedi; N. Collins (Journal of Fish Biology, 2000)
Growth (length, weight) of yellow perch Perca flavescens in western and west‐central Lake Erie began between June and July, possibly reaching asymptotic size by early winter. Energy density (kJ g −1 ) of somatic tissue increased markedly from June to September, then declined to low levels by the following spring. Consequently, energy mass (kJ) of somatic tissue increased to September and then declined slowly until March. Ovarian growth began in October, and the size of the ovaries was maximal in April, just before spawning in May. The energy density of ovaries, however, increased to a peak in December, and then declined. The increase in ovary size in the winter, therefore, resulted largely from an allocation of tissue of low energy density. Fecundity and gonad size were correlated with somatic and gonadal energy density. A bioenergetics model was used to describe the monthly allocations of energy to respiration, growth, excretion, and reproduction. Most direct reproductive costs (80%) were incurred from September to December, corresponding to the cycle in the activity of the liver. Energy acquired in the early summer may be critical for determining maturation, fecundity, and egg quality. From 1978 to 1990,

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

The presence of cross-reactive antibodies to rabbit haemorrhagic disease virus in Australian wild rabbits prior to the escape of virus from quarantine - H. S. Nagesha; K. A. McColl; B. J. Collins; C. J. Morrissy; L. -F. Wang; H. A. Westbury (Archives of Virology, 2000)

Isolation of polymorphic microsatellite loci from the malaria vector Anopheles funestus - S. P. Sinkins; B. J. Hackett; C. Costantini; J. Vulule; Y‐Y. Ling; F. H. Collins; N. J. Besansky (Molecular Ecology, 2000)

Evaluation of anti-cocaine antibodies and a cocaine vaccine in a rat self-administration model - K. M. Kantak; S. L. Collins; E. G. Lipman; J. Bond; K. Giovanoni; B. S. Fox (Psychopharmacology, 2000)

Low levels of DNA sequence variation among adapted genotypes of hexaploid wheat - G. J. Bryan; P. Stephenson; A. Collins; J. Kirby; J. B. Smith; M. D. Gale (Theoretical and Applied Genetics, 1999)

Isolation, genomic organization, and expression analysis of Men1, the murine homolog of the MEN1 gene - Siradanahalli C. Guru; Judy S. Crabtree; Kevin D. Brown; Karen J. Dunn; Pachiappan Manickam; Nijaguna B. Prasad; Danny Wangsa; A. Lee Burns; Allen M. Spiegel; Stephen J. Marx; William J. Pavan; Francis S. Collins; et al. (Mammalian Genome, 1999)

Comparison of intravenous and intranasal heroin self-administration by morphine-maintained humans - S. D. Comer; Eric D. Collins; Robert B. MacArthur; Marian W. Fischman (Psychopharmacology, 1999)

A 200-year coral stable oxygen isotope record from a high-latitude reef off Western Australia - H. Kuhnert; J. Pätzold; B. Hatcher; K.-H. Wyrwoll; A. Eisenhauer; L. B. Collins; Z. R. Zhu; G. Wefer (Coral Reefs, 1999)

Muscle parvalbumin isoforms of Clarias gariepinus, Heterobranchus longifilis and Chrysichthys auratus : isolation, characterization and expression during development - B. Focant; F. Mélot; S. Collin; A. Chikou; P. Vandewalle; F. Huriaux (Journal of Fish Biology, 1999)
The white‐muscle parvalbumin isoforms of Clarias gariepinus, Heterobranchus longifilis and Chrysichthys auratus were purified and their physicochemical parameters determined. The three catfish isoforms are distinct but those of C. gariepinus and H. longifilis are more similar. In the course of development, the successive appearance of larval and adult parvalbumins was observed. Larval isoforms (PA I, PA IIa, PA IIb) displayed a lower isoelectric point (pI) and molecular mass than adult ones (PA IIc, PA IIIa, PA IIIb, PA III, PA IV). The PA IIa isoform appeared as an omnipresent typical larval isoform. PA IIb appeared mostly larval, being insignificant in adult specimens; its physicochemical features were the same in the three catfish species. In Chrysichthys auratus , there were three PA II isoforms, one appearing as an adult isoform (PA IIc). The fact that the two types of parvalbumin isoforms appear at different times should reflect specific physiological needs (mobility, feeding) of different developmental stages.

Morphometric Study of the Equine Navicular Bone: Age-Related Changes and Influence of Exercise - A. Gabriel; J. Detilleux; S. Jolly; J.-Y. Reginster; B. Collin; C. Dessy-Doizé (Veterinary Research Communications, 1999)

Factors affecting soybean cotyledonary node transformation - C. A. Meurer; R. D. Dinkins; G. B. Collins (Plant Cell Reports, 1998)

Localisation of gelatinase activity in epidermal hoof lamellae by in situ zymography - B. A. Mungall; Rita Collins; Christopher C. Pollitt (Histochemistry and Cell Biology, 1998)

Spatial and Temporal Trends in Organochlorine Contamination and Bill Deformities in Double-Crested Cormorants (Phalacrocorax Auritus) from the Canadian Great Lakes - D.P. Ryckman; D.V. Weseloh; P. Hamr; G.A. Fox; B. Collins; P.J. Ewins; R.J. Norstrom (Environmental Monitoring and Assessment, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Simple sequence length polymorphisms (SSLPs) that distinguish MOLF/Ei and 129/Sv inbred strains of laboratory mice - Angabin Matin; Gayle B. Collin; Yoshinobu Asada; Don Varnum; Diana L. Martone; Joseph H. Nadeau (Mammalian Genome, 1998)

Repeated methylphenidate treatment induces behavioral sensitization and decreases protein kinase A and dopamine-stimulated adenylyl cyclase activity in the dorsal striatum - C. A. Crawford; S. A. McDougall; T. L. Meier; R. L. Collins; J. B. Watson (Psychopharmacology, 1998)

Development of a binary vector system for plant transformation based on the supervirulent Agrobacterium tumefaciens strain Chry5 - R. S. Torisky; L. Kovacs; S. Avdiushko; J. D. Newman; A. G. Hunt; G. B. Collins (Plant Cell Reports, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Direct Determination of Drug Content in Semisolid Formulations Using Step-Scan FT-IR Photoacoustic Spectroscopy - R. Neubert; B. Collin; S. Wartewig (Pharmaceutical Research, 1997)

Changes in the fatty acid profile of the Australian shortfin eel in relation to development - S. S. De Silva; R. M. Gunasekera; R. Collins; B. A. Ingram; C. M. Austin (Journal of Fish Biology, 1997)
In glass eels (54 mm TL; 0.018 g) of the Australian shortfin eel Anguilla australis the fatty acid composition was typical of marine species, with a n‐3 to n‐6 ratio of 5.3, a low level of mono saturated fatty acids (monoenes) and a high level of polyunsaturated fatty acids (PUFA). In elvers (pigmented: 56 mm TL; 0.028 g), the n‐3 to n‐6 ratio was 2.6. In elvers monoenes, as per cent of all identifiable fatty acids, increased to 30.9% from that of 19.8% in glass eels. The fatty acid composition of juvenile eels, reared from the original stock of glass eels and elvers, in outdoor, fertilized ponds, with (115 mmTL; 2.2 g) and without feeding (110 mmTL; 1.9 g), had a fatty acid composition typical of freshwater species, with a n‐3 to n‐6 ratio 1.9 and 1.3, and 37.7 and 46.5% of monoenes in unfed and fed groups respectively. A principal component analysis summarized efficiently the progressive changes in fatty acid composition from the glass eel to juvenile eel stage. The observed changes in the fatty acid of the different developmental stages in Australian shortfin eel are discussed in relation to physiological changes associated with the diadromous habit.

Isolation and characterisation of microsatellites from hexaploid bread wheat - G. J. Bryan; A. J. Collins; P. Stephenson; A. Orry; J. B. Smith; M. D. Gale (Theoretical and Applied Genetics, 1997)

Characterization of parvalbumin isotypes in white muscle from the barbel and expression during development - F. Huriaux; S. Collin; P. Vandewalle; J. C. Philippart; B. Focant (Journal of Fish Biology, 1997)
Parvalbumin isotypes PA II, PA III, PA IVa, and PA IVb were isolated by chromatography from trunk white muscle of barbel and physicochemically characterized. Electrospray ionization mass spectroscopy revealed that PA II has a lower molecular weight than the other isotypes and that PA IVa and PA IVb each consist of two subforms. Isotype distribution was studied by polyacrylamide gel electrophoresis. In adult fish, the total parvalbumin titre decreased and the isotype distribution varied from the anterior to the posterior myotomes. In the course of barbel development, the total parvalbumin titre increased rapidly as fish standard length increased from 1·3 to 5 cm; then sloped down gently as the length increased to 60 cm. At least six parvalbumin isotypes were identified, three of which are different forms (a, b, and c) of PA II. These three forms were present together at the larval stage, but PA IIc and chiefly PA IIb appeared as early isotypes, contrary to PA IIa which was present until the adult period. Later PA IVb accounted for up to 90% of the total parvalbumin content; PA III and PA IVa are minor adult isotypes. Temporal and spatial variations in the total parvalbumin titre and in the differential expression of barbel parvalbumin isotypes very likely reflected the functional requirements of the fish axial musculature according to fish size and myotome location. Physiologically, the larval isotypes could promote faster relaxation of fast fibres than the adult isotypes, and hence favour shorter contraction times.

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Extreme resistance to infection by potato virus Y and potato virus X in an advanced hybridSolanum phureja — S. Stenotomum diploid potato population - Roger L. Vallejo; Wanda W. Collins; Rocco D. Schiavone; Steven A. Lommel; J. B. Young (American Journal of Potato Research, 1994)

Genetic interrelationships of proteolyticClostridium botulinum types A, B, and F and other members of theClostridium botulinum complex as revealed by small-subunit rRNA gene sequences - R. A. Hutson; D. E. Thompson; P. A. Lawson; R. P. Schocken-Itturino; E. C. Bttger; M. D. Collins (Antonie van Leeuwenhoek, 1994)

Deduced amino acid sequences at the fusion protein cleavage site of Newcastle disease viruses showing variation in antigenicity and pathogenicity - M. S. Collins; J. B. Bashiruddin; D. J. Alexander (Archives of Virology, 1993)

Identification of aneuploids in Nicotiana tabacum by isozyme banding patterns - Gloria A. Moore; G. B. Collins (Biochemical Genetics, 1982)

Hexachlorobenzene residues and effects on esterase activities in pre-weanling rats after a reciprocal transfer between HCB-treated and control dams - C. E. Mendoza; B. Collins; J. B. Shields; G. W. Laver (Archives of Toxicology, 1978)

Growth in Netted Gem potatoes as influenced by transplanting and by greensprouting - W. B. Collins (American Journal of Potato Research, 1977)

Hexachlorobenzene residues and effects on esterase activities in pre-weanling rats after a reciprocal transfer between HCB-treated and control dams - C. E. Mendoza; B. Collins; J. B. Shields; G. W. Laver (Archives of Toxicology, 1977)

Analysis of growth in Kennebec with emphasis on the relationship between stem number and yield - W. B. Collins (American Journal of Potato Research, 1977)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

The mouse liver aldehyde oxidase locus (Aox) - J. G. Watson; T. J. Higgins; P. B. Collins; S. Chaykin (Biochemical Genetics, 1972)